Metal oxide particles having core-shell structure and method for producing same

CN119301070APending Publication Date: 2025-01-10NISSAN CHEM CORP
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202480002786.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-05-16
Filing Date
2024-04-17
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

该透镜的折射率约为1.50,低于玻璃透镜的约1.52的折射率,所以在近视用透镜的情况下,会有边缘的厚度变厚之类的缺点

Benefits of technology

[0059] The present invention provides modified metal oxide particles in which metal oxide particles containing titanium oxide are used as cores, metal oxide particles other than titanium oxide are used as shells, and the cores are covered with the shells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301070A_ABST
    Figure CN119301070A_ABST
Patent Text Reader

Abstract

Provided are: modified metal oxide particles in which metal oxide particles containing titanium oxide are used as a core, metal oxide particles other than titanium oxide are used as a shell, and the core is covered with the shell such that a part of the core is exposed; and a method for producing the modified metal oxide particles. A core-shell metal oxide particle comprising a core containing metal oxide particles having an average primary particle diameter of 3-100 nm, and a shell covering the surface of the core and containing metal oxide particles having an average primary particle diameter of 1-7 nm, the average primary particle diameter having the relationship (metal oxide particles of the core) > (metal oxide particles of the shell). When the component (a) is titanium oxide and the component (b) is a metal oxide other than titanium oxide, the core is a particle composed of the component (a) or a particle composed of a combination of the component (a) and the component (b), and the shell is a particle composed of the component (b). (metal oxide other than titanium oxide) / (titanium oxide) is in the range of 0.05-1.0 by mass ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to modified metal oxide particles which use metal oxide particles containing titanium oxide as core particles and are coated with metal oxide particles other than titanium oxide, and a method for producing the particles. Background Art

[0002] Plastic moldings are widely used due to their advantages such as light weight, easy processing, and impact resistance. However, due to insufficient hardness, they are easily scratched, easily penetrated by solvents, charged and attract dust, and have insufficient heat resistance, so they have practical disadvantages when used as eyeglass lenses, window materials, etc. In response to this, a proposal has been proposed to apply a "protective film" to plastic moldings. In fact, many types of coating liquids for forming the protective film have been proposed.

[0003] As a method of imparting a hard coating close to an inorganic coating, there is a coating liquid for forming a coating using an organic silicon compound or a hydrolyzate thereof as a main component (resin component or coating film forming component) and using it for eyeglass lenses (see Patent Document 1).

[0004] Since the scratch resistance of the above-mentioned coating liquid for forming a coating film is still unsatisfactory, it has been proposed to further add a silica sol dispersed in a colloid state, and this has been put into practical use for eyeglass lenses (see Patent Document 2).

[0005] However, most of the conventional plastic eyeglass lenses are manufactured by casting and polymerizing diethylene glycol bisallyl carbonate monomers. The refractive index of the lens is about 1.50, which is lower than the refractive index of glass lenses, which is about 1.52. Therefore, in the case of myopia lenses, there are disadvantages such as thicker edge thickness. Therefore, in recent years, monomers with a higher refractive index than diethylene glycol bisallyl carbonate have been developed, and high refractive index resin materials with a refractive index in the range of 1.54 to 1.76 have been proposed (see Patent Documents 3 and 4).

[0006] For such a high-refractive-index resin lens, a method of using a colloidal dispersion of metal oxide fine particles of Sb and Ti as a coating material has been proposed (see Patent Documents 5 and 6).

[0007] In addition, a coating composition is disclosed, which is composed of a silane coupling agent and a stable modified metal oxide sol having a primary particle size of 2 to 100 nm, wherein the modified metal oxide sol contains particles (c), wherein the particles (c) are obtained by using colloidal particles (a) of a metal oxide having a primary particle size of 2 to 60 nm as a core (core body), and the surface of the core body is coated with a coating (b) composed of colloidal particles of an acidic oxide, and the modified metal oxide sol contains (c) in a ratio of 2 to 50% by mass in terms of metal oxide conversion. Then, as a specific example of the colloidal particles used, a modified titanium oxide-zirconium oxide-tin dioxide composite colloid coated with antimony pentoxide containing an alkylamine is disclosed (see Patent Document 7). In addition, a titanium oxide-tin dioxide-zirconium oxide composite colloid stabilized with an alkylamine or a hydroxycarboxylic acid is disclosed (see Patent Document 8).

[0008] [Prior art literature]

[0009] [Patent Document]

[0010] [Patent Document 1] Japanese Patent Application Laid-Open No. 52-16586

[0011] [Patent Document 2] Japanese Patent Application Laid-Open No. 53-111336

[0012] [Patent Document 3] Japanese Patent Application Laid-Open No. 55-13747

[0013] [Patent Document 4] Japanese Patent Application Laid-Open No. 64-54021

[0014] [Patent Document 5] Japanese Patent Application Laid-Open No. 62-151801

[0015] [Patent Document 6] Japanese Patent Application Laid-Open No. 63-275682

[0016] [Patent Document 7] Japanese Patent Application Publication No. 2001-123115

[0017] [Patent Document 8] Japanese Patent Application Laid-Open No. 10-306258 Summary of the invention

[0018] [Problems to be Solved by the Invention]

[0019] Provided are core-shell type metal oxide particles, which are a composition for obtaining a coating having a high refractive index and high formability by nanoimprinting or the like, and are modified metal oxide particles in which metal oxide particles containing titanium oxide are used as a core, metal oxide particles other than titanium oxide are used as a shell, and the shell is coated on the core in a manner that a part of the core is exposed; and a method for producing the same.

[0020] [Methods to solve the problem]

[0021] The present invention, as a first aspect, is a core-shell type metal oxide particle, comprising: a core body containing metal oxide particles having an average primary particle size of 3 to 100 nm, and a shell body containing metal oxide particles having an average primary particle size of 1 to 7 nm covering the surface of the core body, wherein the average primary particle size has a relationship of (metal oxide particles of the core body)>(metal oxide particles of the shell body),

[0022] When the component (a) is titanium oxide and the component (b) is a metal oxide other than titanium oxide, the core is a particle consisting of the component (a) or a particle consisting of a combination of the components (a) and (b), and the shell is a particle consisting of the component (b).

[0023] The core-shell metal oxide particles satisfy the following requirements A and B:

[0024] Requirement A: In a test in which the core-shell type metal oxide particles are brought into contact with a compound having a P—OH bond, NMR observation shows that PO—Ti bonds are formed in the core-shell type metal oxide particles;

[0025] Requirement B: The refractive index of the core-shell type metal oxide particles is 1.85 or more.

[0026] According to a second aspect, the core-shell metal oxide particles according to the first aspect, wherein the component (b) is at least one metal oxide particle selected from the group consisting of zirconium oxide, silicon dioxide, aluminum oxide, tin oxide, zinc oxide, iron oxide, niobium oxide, tantalum oxide, antimony oxide, and tungsten oxide.

[0027] According to a third aspect, in the core-shell type metal oxide particles according to the first aspect or the second aspect, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) is in the range of 0.05 to 1.0.

[0028] As a fourth aspect, the core-shell type metal oxide particle according to any one of the first to third aspects, wherein an intermediate layer is present between the core particle and the shell particle, and the intermediate layer is a metal oxide particle consisting of a combination of at least one selected from the group consisting of zirconium oxide, silicon dioxide, aluminum oxide, tin oxide, zinc oxide, iron oxide, niobium oxide, tantalum oxide, antimony oxide and tungsten oxide as component (D),

[0029] The core-shell type metal oxide particles have a mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) in the range of 0.05 to 1.0.

[0030] As a fifth aspect, the core-shell type metal oxide particle according to any one of the first to fourth aspects, wherein the surface of the core-shell type metal oxide particle is coated with a compound having a P—OH bond or a Si—OH bond.

[0031] As a sixth aspect, the core-shell type metal oxide particle according to any one of the first aspect to the fifth aspect, wherein the compound having a Si-OH bond is at least one silane compound selected from the group consisting of formula (1) to formula (3) or a hydrolyzate thereof,

[0032]

Chemistry 1

[0033] R 1 a Si(R 2 ) 4-a Formula (1)

[0034] 〔R 3 b Si(R 4 ) 3-b 〕2Y c Formula (2)

[0035] R 5 d Si(R 6 ) 4-d Formula (3)

[0036] (In formula (1), R 1 are alkyl, halogenated alkyl, alkenyl, aryl, or an organic group having a polyether group, epoxy group, (meth)acryloyl group, mercapto group, amino group, urea group or cyano group, and R 1 Bonded to silicon atoms through Si-C bonds, R 2 represents an alkoxy group, an acyloxy group or a halogen group, a represents an integer of 1 to 3,

[0037] In formula (2) and formula (3), R 3 and R 5 are alkyl groups having 1 to 3 carbon atoms or aryl groups having 6 to 30 carbon atoms, and R 3 and R 5 Bonded to silicon atoms through Si-C bonds, R 4 and R 6 represents an alkoxy group, an acyloxy group or a halogen group, Y represents an alkylene group, an NH group or an oxygen atom, b is an integer from 1 to 3, c is an integer of 0 or 1, and d is an integer from 1 to 3).

[0038] As a seventh aspect, the core-shell type metal oxide particle according to any one of the first aspect to the fifth aspect, wherein the compound having a P-OH bond is at least one phosphate ester selected from the group consisting of formula (4) to formula (6),

[0039]

Chemistry 2

[0040]

[0041] (In formulas (4) to (6), X1, X2 and X3 represent an alkylene group having 2 to 20 carbon atoms, f, h and j represent integers from 1 to 100, e, g and i represent integers from 1 to 3, Y1, Y2 and Y3 represent a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms or a (meth)acryloyl group, respectively).

[0042] As an eighth aspect, in the core-shell type metal oxide particle according to the seventh aspect, the phosphoric acid ester is a polyoxyethylene alkyl (C6-20) ether phosphoric acid ester having an alkyl group having 6 to 20 carbon atoms.

[0043] As a ninth aspect, a core-shell metal oxide sol is provided, which is a sol obtained by using the core-shell metal oxide particles described in any one of the first to eighth aspects as a dispersant and dispersing them in a dispersion medium composed of an alcohol that may have an ether bond, an ester, a ketone, an amide, a hydrocarbon, a polysilicone, a compound containing unsaturated bonds between chain carbon atoms, an ethylene oxide compound, water, or a combination thereof, wherein the average particle size of the core-shell metal oxide sol measured by a dynamic light scattering method is 5 to 500 nm.

[0044] As a tenth aspect, the core-shell type metal oxide sol according to the ninth aspect further comprises a surfactant, and the surfactant is an anionic surfactant, a cationic surfactant, a nonionic surfactant, or an amphoteric surfactant.

[0045] According to an eleventh aspect, the core-shell type metal oxide sol according to the ninth aspect or the tenth aspect further contains a secondary or tertiary amine having a total carbon number of 5 to 35.

[0046] As a twelfth aspect, a varnish is provided, comprising the core-shell type metal oxide particles according to any one of the first aspect to the eighth aspect, and a thermosetting resin or a photocurable resin.

[0047] As a 13th aspect, the varnish according to the 12th aspect, wherein the varnish is a hard coating agent or a composition for nanoimprint.

[0048] As a 14th aspect, there is provided a method for producing the core-shell type metal oxide sol according to any one of the 9th aspect to the 11th aspect, comprising the following steps (i) and (ii):

[0049] (i) step: preparing a sol (A) and a sol (B), wherein the sol (A) uses water as a dispersion medium and contains metal oxide particles having an average primary particle size of 3 to 60 nm as measured by a nitrogen adsorption method, and the sol (B) uses water as a dispersion medium and contains metal oxide particles having an average primary particle size of 1 to 7 nm as measured by a nitrogen adsorption method;

[0050] (ii) Step: A step of mixing the above-mentioned sol (A) and the above-mentioned sol (B) in the following manner, that is, mixing them at a ratio of 22 to 1000 parts by mass of the solid content of the other sol to be added to the container per minute, relative to 100 parts by mass of the solid content of the sol filled in the container.

[0051] As a fifteenth aspect, the method for producing a core-shell type metal oxide sol according to the fourteenth aspect, wherein in the above step (i) or step (ii), the following step (S-1) is added:

[0052] Step (S-1): a step of adding a secondary or tertiary amine having a total carbon number of 5 to 35 to the aqueous sol.

[0053] As a 16th aspect, the method for producing a core-shell type metal oxide sol according to the 14th aspect or the 15th aspect, wherein after the above step (ii), at least one step selected from the group consisting of the step (T-1), the step (T-2) and the step (T-3) is further added,

[0054] Step (T-1): adding at least one silane compound selected from the group consisting of formula (1) to formula (3) or at least one phosphate ester selected from the group consisting of formula (4) to formula (6) to the core-shell type metal oxide sol obtained in step (ii);

[0055] (T-2) step: a step of replacing the dispersion medium of the core-shell type metal oxide sol obtained in step (ii) with a dispersion medium composed of an alcohol, ester, ketone, amide or hydrocarbon;

[0056] Step (T-3): a step of adding a surfactant to the core-shell type metal oxide sol obtained in step (ii).

[0057] As a 17th aspect, a method for producing a core-shell type metal oxide sol as described in any one of the 14th to 16th aspects is provided, wherein the steps are sequentially (i), (S-1), (ii), (S-1), (T-2), (T-1) and (T-2).

[0058] [Effects of the Invention]

[0059] The present invention provides modified metal oxide particles comprising metal oxide particles containing titanium oxide as a core and metal oxide particles other than titanium oxide as a shell, wherein the core is coated with the shell.

[0060] Titanium oxide has a high refractive index and can be used for high refractive materials. On the other hand, titanium oxide particles are highly photoactive, so when various binders or resin components are mixed as matrix components, the matrix components may be discolored or degraded.

[0061] In order to suppress photoactivity, core-shell type modified metal oxide particles are proposed in which titanium oxide particles are coated with metal oxide particles other than titanium oxide. In core-shell type metal oxide particles, if titanium oxide particles that will become the core or metal oxide particles containing titanium oxide particles are coated with metal oxide particles other than titanium oxide that will become the shell, the ratio of the titanium oxide component is reduced due to complete coating, and the refractive index of the core-shell type metal oxide particles may not be improved.

[0062] In the present invention, in order to maintain a high refractive index in the core-shell type metal oxide particles, the core particles are not completely covered by the shell particles, thereby providing a core-shell type modified metal oxide particle in which a portion of the surface of the core particle is exposed. The partial exposure of the core represents: in a test in which the core-shell type metal oxide particles are contacted with a compound having a P-OH bond, according to the 31 The P-NMR spectrum showed that PO-Ti bonds were formed in the core-shell type metal oxide particles, and it was determined that PO-Ti was "bonded", and it was confirmed that the core-shell type metal oxide particles had a portion of the core exposed.

[0063] In the core-shell metal oxide particles of the present invention, for the core-shell metal oxide particles in which a portion of the surface of the core particle is exposed, particle A having a portion of the surface of the core particle exposed and the same particle B, there will be interaction between the exposed portion of the core particle and the portion of the shell particle, and when coated on a substrate or coated on the uneven portion of the surface of the substrate, the coating or filler will function as an integrated block, thereby achieving, for example, improvement in the weather resistance of a coating on a substrate.

[0064] In addition, if the refractive index of the combined core particles is higher than that of the shell particles, and the refractive index of the shell particles is lower than that of the core particles, and a high-refractive material is made, a sol containing core-shell metal oxide particles with a portion of the surface of the core particles exposed can suppress the decrease in the refractive index of the coating or filler after curing when these sols are used to make a coating or filler because there are no excess shell particles.

[0065] In the present invention, the refractive index of the core-shell type metal oxide particles is 1.85 or more, and can be, for example, in the range of 1.85 to 2.30. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] [ Figure 1 ]pass 31 P-NMR confirms the presence or absence of PO-Ti bonds in the core-shell metal oxide particles in the methanol solvent dispersed sol used in Example 1 31 P-NMR spectrum.

[0067] [ Figure 2 ]pass 31 P-NMR confirms the presence or absence of PO-Ti bonds in the metal oxide particles of the single core body in the methanol solvent dispersed sol used in Comparative Example 1. 31 P-NMR spectrum,.

[0068] [ Figure 3 ]pass 31 P-NMR confirms the presence or absence of PO-Ti bonds in the core-shell type metal oxide particles in the methanol solvent dispersed sol used in Comparative Example 3 31 P-NMR spectrum. DETAILED DESCRIPTION

[0069] The present invention is a core-shell type metal oxide particle, comprising: a core body containing metal oxide particles with an average primary particle size of 3 to 60 nm, and a shell body containing metal oxide particles with an average primary particle size of 1 to 7 nm covering the surface of the core body, wherein the average primary particle size has a relationship of (metal oxide particles of the core body)>(metal oxide particles of the shell body),

[0070] When the component (a) is titanium oxide and the component (b) is a metal oxide other than titanium oxide, the core is a particle consisting of the component (a) or a particle consisting of a combination of the components (a) and (b), and the shell is a particle consisting of the component (b).

[0071] The core-shell metal oxide particles satisfy the following requirements A and B:

[0072] Requirement A: In a test in which the core-shell type metal oxide particles are brought into contact with a compound having a P—OH bond, NMR observation shows that PO—Ti bonds are formed in the core-shell type metal oxide particles;

[0073] Requirement B: The refractive index of the core-shell type metal oxide particles is 1.85 or more.

[0074] In the present invention, the refractive index of the core-shell type metal oxide particles is 1.85 or more, and for example, core-shell type metal oxide particles in the range of 1.85 to 2.30 can be obtained.

[0075] The component (a) is titanium oxide, and the component (b) is at least one metal oxide particle selected from the group consisting of zirconium oxide, silicon dioxide, aluminum oxide, tin oxide, zinc oxide, iron oxide, niobium oxide, tantalum oxide, antimony oxide, and tungsten oxide.

[0076] The core particles are preferably particles consisting of component (a) or a combination of component (a) and component (b), and examples thereof include titanium oxide particles, composite particles of titanium oxide particles and tin oxide particles, composite particles of titanium oxide particles and zirconium oxide particles, and composite particles of titanium oxide particles, tin oxide particles and zirconium oxide particles.

[0077] The shell particles are preferably particles consisting of component (b), and can be at least one metal oxide particle selected from the group consisting of zirconium oxide, silicon dioxide, aluminum oxide, tin oxide, zinc oxide, iron oxide, niobium oxide, tantalum oxide, antimony oxide, and tungsten oxide.

[0078] In the core-shell type metal oxide particles composed of, for example, a combination of core particles and shell particles, the core particles / shell particles may include the following combinations: titanium oxide particles / composite particles of tin oxide and silicon dioxide, composite particles of titanium oxide and tin oxide / composite particles of tin oxide and silicon dioxide, composite particles of titanium oxide particles and zirconium oxide particles / composite particles of tin oxide and silicon dioxide, composite particles of titanium oxide particles, tin oxide particles and zirconium oxide particles / composite particles of tin oxide and silicon dioxide, titanium oxide particles / antimony oxide particles, and composite particles of titanium oxide and tin oxide / antimony oxide particles.

[0079] The mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) of the core-shell type metal oxide particles is in the range of 0.05 to 1.0, or 0.1 to 1.0, or 0.15 to 1.0.

[0080] In the present invention, an intermediate layer exists between the core particles and the shell particles, and the intermediate layer is a metal oxide particle composed of a combination of at least one selected from the group consisting of zirconium oxide, silicon dioxide, aluminum oxide, tin oxide, zinc oxide, iron oxide, niobium oxide, tantalum oxide, antimony oxide, and tungsten oxide as component (D), and the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) is in the range of 0.05 to 1.0, or 0.1 to 1.0, or 0.15 to 1.0.

[0081] Core-shell type metal oxide particles and metal oxide particles having an intermediate layer between the core particle and the shell particle are those in which, in a test in which the oxide particles are in contact with a compound having a P-OH bond, 31 The P-NMR spectrum observed that the metal oxide particles formed particles with PO-Ti bonds. This can be judged that PO-Ti is "bonded" between the core particle and the compound having a P-OH bond, and it can be confirmed that it is a core-shell type metal oxide particle with a portion of the core exposed. It shows: core-shell type metal oxide particles, and metal oxide particles with an intermediate layer between the core particle and the shell particle, and particles with a portion of the core particle exposed.

[0082] The metal oxide particles used for the core body may be titanium oxide, a composite oxide of titanium oxide-tin oxide, a composite oxide of titanium oxide-zirconium oxide, or a composite oxide of titanium oxide-zirconium oxide-tin oxide. These particles have an average primary particle size of 5 to 500 nm, 5 to 300 nm, 5 to 250 nm, or 5 to 60 nm when observed by a transmission electron microscope, and preferably have an average primary particle size of 3 to 100 nm, 3 to 80 nm, 3 to 60 nm, 3 to 40 nm, 3 to 20 nm, or 5 to 40 nm.

[0083] For example, the metal oxide particles used for coating may be at least one metal oxide particle selected from the group consisting of zirconium oxide, silicon dioxide, aluminum oxide, tin oxide, zinc oxide, iron oxide, niobium oxide, tantalum oxide, antimony oxide, and tungsten oxide. These particles have an average primary particle size of 1 to 10 nm, 1 to 7 nm, or 1 to 5 nm as observed by a transmission electron microscope.

[0084] Examples include metal oxide particles in which the above-mentioned silicon dioxide, tin oxide, antimony oxide, tungsten oxide, aluminum oxide and zirconium oxide exist separately, or composite metal oxide particles formed by combining and bonding a plurality of the above-mentioned metal oxides. As composite metal oxide particles, tin oxide-silicon dioxide composite metal oxide particles, tin oxide-zirconium oxide-silicon dioxide composite metal oxide particles, tin oxide-tungsten oxide-silicon dioxide composite metal oxide particles, antimony oxide-silicon dioxide composite metal oxide particles, etc. can be mentioned. In the case where the metal oxide particles used for coating contain silicon dioxide, the ratio of silicon dioxide to other metal oxides can be set to a ratio of 0.1 to 5.0 in terms of the mass ratio of (silicon dioxide) / (other metal oxides).

[0085] When a core-shell structure is used, the coating is performed with metal oxide particles having a different metal oxide composition or a different metal oxide content from the metal oxide of the core (core body), which may include the following situations: the composition of the core and the coated metal oxide is different, or even if the composition of the core and the coated metal oxide is partially repeated, the mixing ratio of the metal oxide is different.

[0086] In the case of a core-shell structure, the mass ratio of the core metal oxide particles to the coated metal oxide particles can be set to a range of (coated metal oxide particles) / (core metal oxide particles)=0.05 to 0.40.

[0087] For example, when a composite oxide of tin oxide and silicon dioxide is used for coating, sodium stannate or potassium stannate can be used as the alkali metal stannate, and sodium stannate is preferred.

[0088] As the alkali metal silicate, sodium silicate or potassium silicate can be used.

[0089] An alkali metal stannate and an alkali metal silicate are prepared so as to form an aqueous solution containing silicon dioxide / tin dioxide at a mass ratio of 0.1 to 5, and then cations present in the aqueous solution may be removed by a cation exchange resin.

[0090] The alkali metal stannate and the alkali metal silicate are dissolved in water and prepared by measuring the mass ratio of silicon dioxide to tin dioxide to be 0.1 to 5.0. The preferred solid content concentration of the aqueous solution is 1 to 12% by mass in terms of (SnO2+SiO2).

[0091] The modulated aqueous solution can be treated with a cation exchange resin to remove cations. The cation exchange resin is preferably a hydrogen-type strongly acidic cation exchange resin, such as Amberlite (trade name) 120B, which can be filled into a column for use. By performing the cation exchange, the silicate component and the stannic acid component are polymerized to generate silica-tin dioxide composite colloidal particles having an average primary particle size of 1 to 4 nm.

[0092] The silica-tin oxide composite colloidal particles lack stability and will gel after being left for several hours. Therefore, an amine compound must be added immediately after cation exchange to stabilize them. The amine compound must be present in a silica / tin oxide mass ratio of 0.1 to 5.0 and a molar ratio of M / (SnO2+SiO2) (wherein M represents an amine compound) of 0.1 to 1.0 to prepare an aqueous sol of stabilized silica-tin oxide composite colloidal particles having an average primary particle size of 1 to 4 nm. The obtained aqueous sol has a (SnO2+SiO2) content of 0.1 to 10% by mass.

[0093] Regarding the stabilization of the silica-tin dioxide composite colloidal particles generated by the above-mentioned cation exchange, it is appropriate to add an amine compound in an amount of 0.1 to 1.0 as a molar ratio of M / (SnO2+SiO2) (wherein M represents an amine compound). If the amine compound is added in a manner such that the molar ratio of M / (SnO2+SiO2) is less than 0.1 to 1.0, it will lose stability and gel after being left for several hours, so it is not preferred.

[0094] Next, an aqueous sol of metal oxide colloidal particles (a) having an average primary particle size of 5 to 60 nm used as a core is mixed with an aqueous sol of silica-tin dioxide composite oxide colloidal particles (b) having an average primary particle size of 1 to 4 nm, which are stabilized by an amine compound having a silica / tin dioxide mass ratio of 0.1 to 5.0 (wherein M represents an amine compound) used as a shell, at a mass ratio of the silica-tin dioxide composite oxide colloidal particles to the metal oxide colloidal particles ((b) / (a)) of 0.05 to 0.40. This can produce an aqueous sol of modified metal oxide colloidal particles in which the metal oxide colloidal particles (a) are coated with the silica-tin dioxide composite oxide colloidal particles (b).

[0095] The solid content concentration of the aqueous sol of the metal oxide colloidal particles (a) is 0.5 to 50% by mass, preferably 5 to 30% by mass.

[0096] The aqueous sol of the metal oxide colloidal particles (a) can be used at a pH of 5 to 11.5, preferably 7 to 11.5. The pH of the aqueous sol can be adjusted by an alkali component as required, and examples of the alkali component include alkali metal hydroxides such as lithium, sodium, and potassium, alkaline earth metal hydroxides such as calcium, magnesium, and strontium, ammonia, alkylamines such as ethylamine, triethylamine, isopropylamine, and n-propylamine, arylalkylamines such as benzylamine, alicyclic amines such as piperidine, alkanolamines such as monoethanolamine and triethanolamine, and quaternary ammonium hydroxides.

[0097] The mixing of the aqueous sol of the metal oxide colloidal particles (a) and the aqueous sol of the coated particles (b) is preferably performed under stirring.

[0098] The mixing ratio of the silica-tin dioxide composite oxide colloidal particles (b) to the metal oxide colloidal particles (a) is preferably 0.05 to 0.40 in terms of mass ratio (b) / (a). If it is less than 0.05, the metal oxide colloidal particles (a) serving as the core (core body) cannot be sufficiently covered with the silica-tin dioxide composite oxide colloidal particles (b), and a stable hydrophilic organic solvent dispersion sol or a hydrophobic organic solvent dispersion sol having a water solubility of 0.05 to 12 mass % cannot be obtained. On the other hand, the mass ratio is sufficient to be 0.40 or more, and complete coverage may be achieved.

[0099] Next, the obtained aqueous sol of modified metal oxide colloidal particles is subjected to cation exchange. For the cation exchange, a hydrogen-type strongly acidic cation exchange resin is preferably used.

[0100] Next, an amine compound is added to the obtained aqueous sol in an amount such that the molar ratio of the amine compound to the silica-tin dioxide composite oxide colloidal particles (b) is 0.001 to 0.08, M / (SnO2+SiO2) (wherein M represents an amine compound). If the amount of the amine compound added is less than 0.001 in terms of the molar ratio of M / (SnO2+SiO2), the dispersion stability of the hydrophilic organic solvent dispersion sol of the present invention becomes insufficient, which is not preferred. In addition, if the molar ratio of M / (SnO2+SiO2) exceeds 0.08, the silane compound to be bonded to the particle surface of the modified metal oxide colloidal particles may be hindered from bonding.

[0101] The metal oxide particles of the present invention are obtained via a metal oxide sol.

[0102] The metal oxide sol can be obtained by the following method.

[0103] An example of a method for producing a core-shell type metal oxide sol is a method comprising the following steps (i) and (ii):

[0104] (i) step: a step of preparing a sol (A) and a sol (B), wherein the sol (A) uses water as a dispersion medium and contains metal oxide particles having an average primary particle size of 3 to 60 nm as measured by a nitrogen adsorption method, and the sol (B) uses water as a dispersion medium and contains metal oxide particles having an average primary particle size of 1 to 7 nm as measured by a nitrogen adsorption method;

[0105] (ii) Step: A step of mixing the above-mentioned sol (A) and the above-mentioned sol (B) in the following manner, that is, mixing them in a ratio of 22 to 1000 parts by mass, or 22 to 500 parts by mass, or 22 to 100 parts by mass of the solid content of the other sol to be added to the container per minute, relative to 100 parts by mass of the solid content of the sol filled in the container.

[0106] The sol (A) is an aqueous sol containing the core particles, and the sol (B) is an aqueous sol containing the shell particles.

[0107] In the present invention, in the above step (i) or step (ii), a step (S-1) of adding a secondary or tertiary amine having a total carbon number of 5 to 35 to the aqueous sol may be added.

[0108] In the present invention, after the above step (ii), at least one step selected from the group consisting of the step (T-1), the step (T-2) and the step (T-3) may be further added.

[0109] The step (T-1) is a step of adding at least one silane compound selected from the group consisting of formulae (1) to (3) or at least one phosphate ester selected from the group consisting of formulae (4) to (6) to the core-shell type metal oxide sol obtained in the step (ii).

[0110] The step (T-2) is a step of replacing the dispersion medium of the core-shell type metal oxide sol obtained in the step (ii) with a dispersion medium composed of an alcohol, ester, ketone, amide or hydrocarbon.

[0111] The step (T-3) is a step of adding a surfactant to the core-shell type metal oxide sol obtained in the step (ii).

[0112] In the present invention, the steps may be sequentially (i), (S-1), (ii), (S-1), (T-2), (T-1), and (T-2).

[0113] In addition, the step (T-3) can be added to any step.

[0114] In the present invention, a secondary amine or a tertiary amine having a total carbon number of 5 to 35 may be further contained.

[0115] The content of the amine can be set to 0.01 to 10.0 mmol, or 0.01 to 5.0 mmol, relative to 100 g of SiO 2 in the silica particles.

[0116] Examples of the secondary amine include ethyl-n-propylamine, ethyl-isopropylamine, dipropylamine, diisopropylamine, ethyl-butylamine, n-propyl-butylamine, dibutylamine, ethyl-pentylamine, n-propyl-pentylamine, isopropyl-pentylamine, dipentylamine, ethyl-octylamine, isopropyl-octylamine, butyl-octylamine, and dioctylamine.

[0117] Examples of the tertiary amine include triethylamine, ethyldi-n-propylamine, diethyl-n-propylamine, tri-n-propylamine, triisopropylamine, ethyldibutylamine, diethylbutylamine, isopropyldibutylamine, diisopropylethylamine, diisopropylbutylamine, tributylamine, ethyldipentylamine, diethylpentylamine, tripentylamine, methyldioctylamine, dimethyloctylamine, ethyldioctylamine, diethyloctylamine, trioctylamine, benzyldibutylamine, and diazabicycloundecene.

[0118] Among the above amines, secondary and tertiary amines having an alkyl group having 6 to 35 carbon atoms in total are preferred, and examples thereof include diisopropylamine, tripentylamine, triisopropylamine, dimethyloctylamine, and trioctylamine.

[0119] In the present invention, the silane compound is a silane coupling agent, and the silane coupling agent can coat the photoactive metal oxide particles (A) of the present invention with a hydrolyzate of at least one silane compound selected from the group consisting of formula (1) to formula (3).

[0120] The obtained hydrophilic organic solvent-dispersed sol may be coated with a hydrolyzate of at least one silane compound selected from the group consisting of formula (1) to formula (3).

[0121] In formula (1), R 1 are alkyl, halogenated alkyl, alkenyl, aryl, or an organic group having a polyether group, epoxy group, (meth)acryloyl group, mercapto group, amino group, urea group, or cyano group, and R 1 Those bonded to silicon atoms through Si-C bonds, R 2 represents an alkoxy group, an acyloxy group, or a halogen group, and a represents an integer of 1 to 3;

[0122] In formula (2) and formula (3), R 3 and R 5 are alkyl groups having 1 to 3 carbon atoms or aryl groups having 6 to 30 carbon atoms, and R 3 and R5 Those bonded to silicon atoms through Si-C bonds, R 4 and R 6 represents an alkoxy group, an acyloxy group, or a halogen group, Y represents an alkylene group, an NH group, or an oxygen atom, b is an integer of 1 to 3, c is an integer of 0 or 1, and d is an integer of 1 to 3.

[0123] The alkyl group is an alkyl group having 1 to 18 carbon atoms, and examples thereof include methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, 1-methyl-cyclopropyl, 2-methyl-cyclopropyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, 1,2-dimethyl-n-propyl, 2,2-dimethyl-n-propyl, 1-ethyl-n-propyl, cyclopentyl, 1-methyl-cyclobutyl, 2-methyl-cyclobutyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, 1,2-dimethyl-n-propyl, 2,2-dimethyl-n-propyl, 1-ethyl-n-propyl, cyclopentyl, 1-methyl-cyclobutyl, 2-methyl-cyclobutyl, 3-methyl-cyclobutyl, 1, 2-Dimethyl-cyclopropyl, 2,3-dimethyl-cyclopropyl, 1-ethyl-cyclopropyl, 2-ethyl-cyclopropyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl-n-butyl, 2,2-dimethyl-n-butyl, 2,3-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1-ethyl-n-butyl, 2-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, 1, 2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl, 1-ethyl-2-methyl-n-propyl, cyclohexyl, 1-methyl-cyclopentyl, 2-methyl-cyclopentyl, 3-methyl-cyclopentyl, 1-ethyl-cyclobutyl, 2-ethyl-cyclobutyl, 3-ethyl-cyclobutyl, 1,2-dimethyl-cyclobutyl, 1,3-dimethyl-cyclobutyl, 2,2-dimethyl-cyclobutyl, 2,3-dimethyl-cyclobutyl, 2,4-dimethyl-cyclobutyl, 3,3-dimethyl-cyclobutyl, 1-n-propyl-cyclopropyl, 2-n-propyl- Cyclopropyl, 1-isopropyl-cyclopropyl, 2-isopropyl-cyclopropyl, 1,2,2-trimethyl-cyclopropyl, 1,2,3-trimethyl-cyclopropyl, 2,2,3-trimethyl-cyclopropyl, 1-ethyl-2-methyl-cyclopropyl, 2-ethyl-1-methyl-cyclopropyl, 2-ethyl-2-methyl-cyclopropyl and 2-ethyl-3-methyl-cyclopropyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl and the like are not limited thereto.

[0124] In addition, examples of the alkylene group include those derived from the above-mentioned alkyl groups.

[0125] The aryl group is an aryl group having 6 to 30 carbon atoms, and examples thereof include phenyl, naphthyl, onionyl, pyrenyl and the like.

[0126] Examples of the alkenyl group include vinyl, 1-propenyl, 2-propenyl, 1-methyl-1-vinyl, 1-butenyl, 2-butenyl, 3-butenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, 1-ethylvinyl, 1-methyl-1-propenyl, 1-methyl-2-propenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-n-propylvinyl, 1-methyl-1-butenyl, 1-methyl-2-butenyl, 1-methyl-3-butenyl, 2-ethyl-2-propenyl, 2-methyl-1-butenyl, 2-methyl-2-butenyl, 2-methyl-3-butenyl, The above-mentioned groups include, but are not limited to, alkenyl, 3-methyl-1-butenyl, 3-methyl-2-butenyl, 3-methyl-3-butenyl, 1,1-dimethyl-2-propenyl, 1-isopropylvinyl, 1,2-dimethyl-1-propenyl, 1,2-dimethyl-2-propenyl, 1-cyclopentenyl, 2-cyclopentenyl, 3-cyclopentenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 4-hexenyl, 5-hexenyl, 1-methyl-1-pentenyl, 1-methyl-2-pentenyl, 1-methyl-3-pentenyl, 1-methyl-4-pentenyl, 1-n-butylvinyl, 2-methyl-1-pentenyl, and 2-methyl-2-pentenyl.

[0127] The alkoxy group includes alkoxy groups having 1 to 10 carbon atoms, such as methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, n-pentoxy, 1-methyl-n-butoxy, 2-methyl-n-butoxy, 3-methyl-n-butoxy, 1,1-dimethyl-n-propoxy, 1,2-dimethyl-n-propoxy, 2,2-dimethyl-n-propoxy, 1-ethyl-n-propoxy, n-hexyloxy, etc., but is not limited to these.

[0128] The acyloxy group is an acyloxy group having 2 to 10 carbon atoms, and examples thereof include, but are not limited to, a methylcarbonyloxy group, an ethylcarbonyloxy group, an n-propylcarbonyloxy group, an isopropylcarbonyloxy group, an n-butylcarbonyloxy group, an isobutylcarbonyloxy group, a sec-butylcarbonyloxy group, a tert-butylcarbonyloxy group, an n-pentylcarbonyloxy group, a 1-methyl-n-butylcarbonyloxy group, a 2-methyl-n-butylcarbonyloxy group, a 3-methyl-n-butylcarbonyloxy group, a 1,1-dimethyl-n-propylcarbonyloxy group, a 1,2-dimethyl-n-propylcarbonyloxy group, a 2,2-dimethyl-n-propylcarbonyloxy group, a 1-ethyl-n-propylcarbonyloxy group, an n-hexylcarbonyloxy group, a 1-methyl-n-pentylcarbonyloxy group, and a 2-methyl-n-pentylcarbonyloxy group.

[0129] Examples of the halogen group include fluorine, chlorine, bromine, and iodine.

[0130] As the organic group having a polyether group, a polyether propyl group having an alkoxy group can be mentioned. For example, (CH3O)3SiC3H6(OC2H4)nOCH3 can be mentioned. n can be in the range of 1 to 100, or 1 to 10.

[0131] Examples of the organic group having an epoxy group include a 2-(3,4-epoxycyclohexyl)ethyl group and a 3-glycidyloxypropyl group.

[0132] The (meth)acryloyl group refers to both an acryloyl group and a methacryloyl group. Examples of the organic group having a (meth)acryloyl group include a 3-methacryloyloxypropyl group and a 3-acryloyloxypropyl group.

[0133] Examples of the organic group having a mercapto group include a 3-mercaptopropyl group.

[0134] Examples of the organic group having an amino group include a 2-aminoethyl group, a 3-aminopropyl group, an N-2-(aminoethyl)-3-aminopropyl group, an N-(1,3-dimethylbutylene)aminopropyl group, an N-phenyl-3-aminopropyl group, and an N-(vinylbenzyl)-2-aminoethyl-3-aminopropyl group.

[0135] Examples of the organic group having a ureido group include a 3-ureidopropyl group.

[0136] Examples of the organic group having a cyano group include a 3-cyanopropyl group.

[0137] The above formula (2) and formula (3) are preferably compounds capable of forming a trimethylsilyl group on the surface of silica particles.

[0138] Examples of these compounds include the following.

[0139]

Chemistry 3

[0140]

[0141] In the above formula, R 12 The alkoxy group includes, for example, a methoxy group and an ethoxy group. As the silane compound, a silane compound manufactured by Shin-Etsu Chemical Co., Ltd. can be used.

[0142] The process of coating the surface of the silica particles with the silane compound through a hydroxyl group, for example, a silanol group in the case of silica particles, and a siloxane bond. The reaction temperature can be carried out at a temperature ranging from 20°C to the boiling point of the dispersion medium, for example, in the range of 20°C to 100°C. The reaction time can be about 0.1 to 6 hours.

[0143] The coating amount of the silicon dioxide particle surface with the silane compound can be set to 0.1 silicon atoms / nm in the silane compound. 2 ~6.0 / nm 2 The silane compound is added to the silica sol in a coating amount of 1000 Å to coat the surface of the silica particles.

[0144] Water is essential for the hydrolysis of the above-mentioned silane compound. If it is a sol of an aqueous solvent, these aqueous solvents can be used. When the aqueous solvent is solvent-substituted with an organic solvent (C), the water in the residual solvent can be used. For example, water present in an amount of 0.01 to 1% by mass can be used. In addition, the hydrolysis can be carried out using a catalyst or in the absence of a catalyst.

[0145] When the reaction is carried out without a catalyst, there are acidic sites on the surface of the silica particles. When a catalyst is used, metal chelate compounds, organic acids, inorganic acids, organic bases, and inorganic bases can be cited as hydrolysis catalysts. Metal chelate compounds as hydrolysis catalysts include triethoxy mono(acetylacetonate)titanium, triethoxy mono(acetylacetonate)zirconium, etc. Organic acids as hydrolysis catalysts include acetic acid, oxalic acid, etc. Inorganic acids as hydrolysis catalysts include hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, phosphoric acid, etc. Organic bases as hydrolysis catalysts include pyridine, pyrrole, piperazine, and quaternary ammonium salts. Inorganic bases as hydrolysis catalysts include ammonia, sodium hydroxide, and potassium hydroxide.

[0146] The organic acid is at least one organic acid selected from the group consisting of divalent aliphatic carboxylic acids, aliphatic hydroxycarboxylic acids, amino acids and chelating agents. The divalent aliphatic carboxylic acids are oxalic acid, malonic acid and succinic acid. The aliphatic hydroxycarboxylic acids are glycolic acid, lactic acid, malic acid, tartaric acid and citric acid. The amino acids are glycine, alanine, valine, leucine, serine and threonine. The chelating agents include ethylenediaminetetraacetic acid, L-aspartic acid-N,N-diacetic acid and diethylenetriaminepentaacetic acid. The organic acid salts include alkali metal salts, ammonium salts and amine salts of the above organic acids. The alkali metals include sodium and potassium.

[0147] In addition, examples of the phosphoric acid ester that can be used in the present invention include at least one phosphoric acid ester compound selected from the group consisting of formula (4) to formula (6).

[0148] In formulae (4) to (6), X1, X2 and X3 respectively represent an alkylene group having 2 to 20 carbon atoms, f, h and j respectively represent an integer from 1 to 100, e, g and i respectively represent an integer from 1 to 3, and Y1, Y2 and Y3 respectively represent a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms or a (meth)acryloyl group.

[0149] As the phosphoric acid ester, polyoxyethylene alkyl (C6-20) ether phosphoric acid ester having an alkyl group having 6 to 20 carbon atoms can be used.

[0150] The phosphate ester is preferably a polyoxyethylene alkyl ether phosphate, and the phosphate ester can be a phosphate ester having a terminal alkyl group (Y1) of the above formula (4) with a carbon number of 6 to 10 or 12 to 15. For example, products such as Phosphanol RA-600 and RS-610 manufactured by Toho Chemical Industry Co., Ltd. can be used.

[0151] The present invention provides a core-shell metal oxide sol, which is a sol obtained by using core-shell metal oxide particles as a dispersoid and dispersing them in a dispersion medium consisting of an alcohol, ester, ketone, amide, hydrocarbon, polysiloxane, a compound containing an unsaturated bond between chain carbon atoms, an ethylene oxide compound, water, or a combination thereof, wherein the average particle size of the sol measured by a dynamic light scattering method is 5 to 500 nm, or 10 to 200 nm, or 10 to 100 nm, or 10 to 60 nm, or 10 to 40 nm, or 10 to 30 nm.

[0152] The dispersion medium used in the present invention is water and an organic solvent. The organic solvent includes, as alcohols having 1 to 10 carbon atoms, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, n-pentanol, ethylene glycol, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether and the like.

[0153] The ketone is a linear or cyclic aliphatic ketone having 3 to 30 carbon atoms, and examples thereof include methyl ethyl ketone, diethyl ketone, methyl propyl ketone, methyl isobutyl ketone, diisopropyl ketone, diisobutyl ketone, methyl amyl ketone, and cyclohexanone.

[0154] The ether is a linear or cyclic aliphatic ether having 3 to 30 carbon atoms, and examples thereof include diethyl ether and tetrahydrofuran.

[0155] The ester is a linear or cyclic ester having 2 to 30 carbon atoms, and examples thereof include ethyl acetate, n-butyl acetate, sec-butyl acetate, methoxybutyl acetate, amyl acetate, n-propyl acetate, isopropyl acetate, ethyl lactate, butyl lactate, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, phenyl acetate, phenyl lactate, and phenyl propionate.

[0156] The amide is an aliphatic amide having 3 to 30 carbon atoms, and examples thereof include dimethylacetamide, dimethylformamide, N-methylpyrrolidone, and N-ethylpyrrolidone.

[0157] The hydrocarbon is a linear or cyclic aliphatic or aromatic hydrocarbon having 6 to 30 carbon atoms, and examples thereof include hexane, heptane, octane, nonane, decane, benzene, toluene, and xylene.

[0158] As the surfactant used in the present invention, an anionic surfactant, a cationic surfactant, an amphoteric surfactant, and a nonionic surfactant can be used.

[0159] Examples of the anionic surfactant used in the present invention include sodium and potassium salts of fatty acids, alkylbenzene sulfonates, higher alcohol sulfates, polyoxyethylene alkyl ether sulfates, α-sulfonic fatty acid esters, α-olefin sulfonates, monoalkyl phosphates, and alkane sulfonates.

[0160] For example, the alkylbenzene sulfonate includes sodium salt, potassium salt and lithium salt, such as sodium C10-C16 alkylbenzene sulfonate, C10-C16 alkylbenzene sulfonic acid, sodium alkylnaphthalene sulfonate and the like.

[0161] Higher alcohol sulfuric acid ester salts, such as sodium dodecyl sulfate (sodium lauryl sulfate) having 12 carbon atoms, triethanolamine lauryl sulfate, triethanolammonium lauryl sulfate, etc.

[0162] Polyoxyethylene alkyl ether sulfates, such as polyoxyethylene styrene phenyl ether sodium sulfate, polyoxyethylene styrene phenyl ether ammonium sulfate, polyoxyethylene decyl ether sodium sulfate, polyoxyethylene decyl ether ammonium sulfate, polyoxyethylene lauryl ether sodium sulfate, polyoxyethylene lauryl ether ammonium sulfate, polyoxyethylene tridecyl ether sodium sulfate, polyoxyethylene oleyl cetyl ether sodium sulfate, etc.

[0163] α-olefin sulfonates, such as sodium α-olefin sulfonate and the like.

[0164] Examples of the alkane sulfonate include sodium 2-ethylhexyl sulfate and the like.

[0165] Examples of the cationic surfactant used in the present invention include alkyltrimethylammonium salts, dialkyldimethylammonium salts, alkyldimethylbenzylammonium salts, and amine salt-based surfactants.

[0166] The alkyl trimethyl ammonium salt is a quaternary ammonium salt having a chloride ion or a bromide ion as a counter ion, and examples thereof include dodecyl trimethyl ammonium chloride, hexadecyl trimethyl ammonium chloride, coconut oil alkyl trimethyl ammonium chloride, and alkyl (C16-18) trimethyl ammonium chloride.

[0167] Dialkyldimethylammonium salts are ammonium salts having two lipophilic main chains and two methyl groups. Examples include di(hydrogenated tallow)dimethylammonium chloride. Examples include didecyldimethylammonium chloride, dicoconut oil alkyldimethylammonium chloride, dihydrogenated tallow alkyldimethylammonium chloride, and dialkyl(C14-18)dimethylammonium chloride.

[0168] Alkyl dimethyl benzyl ammonium salt is a quaternary ammonium salt having one lipophilic main chain, two methyl groups and a benzyl group. Examples thereof include benzalkonium chloride and alkyl (C8-18) dimethyl benzyl ammonium chloride.

[0169] The amine salt system includes an amine salt in which one or more hydrogen atoms of ammonia are substituted with hydrocarbon groups, and an example thereof is N-methylbishydroxyethylamine fatty acid ester hydrochloride.

[0170] The amphoteric active agent used in the present invention includes alkylamino fatty acid salts of N-alkyl-β-alanine type, alkyl betaines of alkyl carboxy betaine type, and alkyl amine oxides of N,N-dimethyl dodecylamine oxide type. Examples thereof include lauryl betaine, stearyl betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazoline betaine, and lauryl dimethyl amine oxide.

[0171] The nonionic surfactant used in the present invention includes polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, alkyl glucosides, polyoxyethylene fatty acid esters, sucrose fatty acid esters, sorbitol fatty acid esters, polyoxyethylene sorbitol fatty acid esters, and fatty acid alkanolamides. For example, polyoxyethylene alkyl ethers include polyoxyethylene dodecyl ether (polyoxyethylene lauryl ether), polyoxyalkylene lauryl ether, polyoxyethylene tridecyl ether, polyoxyalkylene tridecyl ether, polyoxyethylene myristyl ether, polyoxyethylene cetyl ether, polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene behenyl ether, polyoxyethylene-2-ethylhexyl ether, polyoxyethylene isodecyl ether, and the like.

[0172] Examples of the polyoxyethylene alkylphenol ethers include polyoxyethylene styrenated phenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene distyrenated phenyl ether, and polyoxyethylene tribenzylphenyl ether.

[0173] Examples of the alkyl glucoside include decyl glucoside and lauryl glucoside.

[0174] Examples of the polyoxyethylene fatty acid ester include polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene monooleate, polyethylene glycol distearate, polyethylene glycol dioleate, and polypropylene glycol dioleate.

[0175] Examples of the sorbitan fatty acid esters include sorbitan monocaprylate, sorbitan monolaurate, sorbitan monomyristate, sorbitan monopalmitate, sorbitan monostearate, sorbitan distearate, sorbitan tristearate, sorbitan monooleate, sorbitan trioleate, sorbitan monosesquioleate, and ethylene oxide adducts thereof.

[0176] Examples of the polyoxyethylene sorbitan fatty acid esters include polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, and polyoxyethylene sorbitan triisostearate.

[0177] Examples of fatty acid alkanolamides include coconut oil fatty acid diethanolamide, tallow acid diethanolamide, lauric acid diethanolamide, and oleic acid diethanolamide.

[0178] Furthermore, polyoxyalkyl ethers or polyoxyalkyl glycols such as polyoxyethylene polyoxypropylene glycol and polyoxyethylene fatty acid esters, polyoxyethylene hydrogenated castor oil ethers, sorbitan fatty acid ester alkyl ethers, alkyl polyglucosides, sorbitan monooleate, and sucrose fatty acid esters can be mentioned.

[0179] In the present invention, a composition (varnish) containing core-shell type metal oxide particles and a thermosetting or photocurable resin can be obtained.

[0180] The composition of the present invention can be further mixed with a thermosetting or photocurable resin to produce a varnish.

[0181] In the present invention, a film-forming composition comprising the organic solvent sol and an organic resin can be obtained. The film-forming composition can be obtained by removing the organic solvent from the organic solvent sol to form a film-forming composition comprising core-shell type metal oxide particles and an organic resin.

[0182] In the above-mentioned film-forming composition, if it is a thermosetting film-forming composition, a thermosetting agent in the range of 0.01 to 50 phr, or 0.01 to 10 phr can be added to the resin containing a functional group such as an epoxy group or a (meth)acryloyl group. For example, the thermosetting agent can be contained in a ratio of 0.5 to 1.5 equivalents, preferably 0.8 to 1.2 equivalents to the functional group such as the epoxy group or the (meth)acryloyl group. The equivalent of the thermosetting agent relative to the curable resin is expressed as an equivalent ratio of the thermosetting agent relative to the functional group.

[0183] Examples of the thermosetting agent include phenol resins, amine curing agents, polyamide resins, imidazoles, polythiols, acid anhydrides, thermal radical generators, thermal acid generators, etc. Radical generator curing agents, acid anhydride curing agents, and amine curing agents are particularly preferred.

[0184] Even if these thermosetting agents are solid, they can be used by dissolving them in a solvent. However, since evaporation of the solvent may reduce the density of the cured product or generate pores, resulting in reduced strength and reduced water resistance, the curing agent itself is preferably liquid at room temperature and pressure.

[0185] Examples of the phenol resin include phenol novolac resin and cresol novolac resin.

[0186] Examples of the amine curing agent include piperidine, N,N-dimethylpiperazine, triethylenediamine, 2,4,6-tris(dimethylaminomethyl)phenol, dimethylbenzylamine, 2-(dimethylaminomethyl)phenol, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, N-aminoethylpiperazine, di(1-methyl-2-aminocyclohexyl)methane, menthanediamine, isophoronediamine, diaminodicyclohexylmethane, 1,3-diaminomethylcyclohexane, xylenediamine, meta-phenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, 3,3'-diethyl-4,4'-diaminodiphenylmethane, and diethyltoluenediamine. Among these curing agents, liquid diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, N-aminoethylpiperazine, di(1-methyl-2-aminocyclohexyl)methane, menthanediamine, isophoronediamine, diaminodicyclohexylmethane, 3,3′-diethyl-4,4′-diaminodiphenylmethane, diethyltoluenediamine and the like are preferably used.

[0187] The polyamide resin is a product produced by condensation of a dibasic acid and a polyamine and is a polyamidoamine having a primary amine and a secondary amine in a molecule.

[0188] Examples of the imidazoles include 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, and epoxyimidazole adducts.

[0189] The polythiol includes, for example, a substance having a thiol group at the end of a polypropylene glycol chain or a substance having a thiol group at the end of a polyethylene glycol chain, and is preferably in a liquid state.

[0190] As the acid anhydride curing agent, anhydrides of compounds having a plurality of carboxyl groups in one molecule are preferred. Examples of these acid anhydride curing agents include phthalic anhydride, trimellitic anhydride, pyromellitic dianhydride, diphenyl ketone tetracarboxylic anhydride, ethylene glycol ditrimellitate, glycerol trimellitate, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, endomethylenetetrahydrophthalic anhydride, methylendomethylenetetrahydrophthalic anhydride, methylbutenetetrahydrophthalic anhydride, dodecenylsuccinic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, succinic anhydride, methylcyclohexene dicarboxylic anhydride, and chlorobridged anhydride.

[0191] Examples of the thermal acid generator include sulfonium salts, As the onium salt, preferably a sulfonium salt is used. Examples thereof include the following compounds.

[0192]

Chemistry 4

[0193]

[0194] R includes an alkyl group having 1 to 12 carbon atoms and an aryl group having 6 to 20 carbon atoms, and an alkyl group having 1 to 12 carbon atoms is particularly preferred.

[0195] Among these, methyltetrahydrophthalic anhydride, methyl-5-norbornene-2,3-dicarboxylic anhydride (methyl nadic anhydride, methyl himic anhydride), hydrogenated methylnadic anhydride, methylbutylene tetrahydrophthalic anhydride, dodecenyl succinic anhydride, methylhexahydrophthalic anhydride, and a mixture of methylhexahydrophthalic anhydride and hexahydrophthalic anhydride, which are liquid at room temperature and pressure, are preferred. The viscosity of these liquid anhydrides is about 10 mPa·s to 1000 mPa·s when measured at 25°C.

[0196] Examples of the thermal radical generator include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, tert-butyl hydroperoxide, cumene hydroperoxide, di-tert-butyl peroxide, dicumyl peroxide, and benzoyl peroxide. These can be obtained from Tokyo Chemical Industry Co., Ltd.

[0197] In addition, when obtaining the above-mentioned cured product, a curing aid may be used in combination as appropriate. Examples of the curing aid include organic phosphorus compounds such as triphenylphosphine or tributylphosphine, ethyltriphenylphosphine bromide, , methyltriphenyl Diethyl phosphate and other quaternary Quaternary ammonium salts such as 1,8-diazabicyclo(5,4,0)undec-7-ene, 1,8-diazabicyclo(5,4,0)undec-7-ene and octanoic acid salts, zinc octanoate, and tetrabutylammonium bromide can be contained in an amount of 0.001 to 0.1 parts by mass based on 1 part by mass of the curing agent.

[0198] The composition can be obtained by mixing the resin, the curing agent, and a desired curing aid to obtain a thermosetting varnish. The mixing can be performed in a reaction vessel using a stirring blade or a kneader.

[0199] The mixing can be performed by a heat mixing method at a temperature of 60° C. to 100° C. for 0.5 to 1 hour.

[0200] The obtained curable film-forming composition is a thermosetting coating composition, having a suitable viscosity for use as, for example, a liquid sealant. The liquid thermosetting film-forming composition can be modulated into any viscosity, and since it can be used as a transparent sealant for LEDs, etc., by a casting method, an encapsulation method, a dispenser method, a printing method, etc., a local seal can be performed at any position thereof. The liquid thermosetting composition is directly encapsulated in an LED, etc., in a liquid state by the above-mentioned method, and then dried and cured, thereby obtaining an epoxy resin cured body.

[0201] A cured product can be obtained by applying a thermosetting film-forming composition (thermosetting coating composition) to a substrate and heating the substrate at a temperature of 80 to 200°C.

[0202] In the above-mentioned film-forming composition, if it is a photocurable resin composition, a photocuring agent (photoradical generator, photoacid generator) in the range of 0.01 to 50 phr, or 0.01 to 10 phr may be added to the resin containing a functional group such as an epoxy group or a (meth)acryloyl group. For example, the photocuring agent (photoradical generator, photoacid generator) may be contained in a ratio of 0.5 to 1.5 equivalents, preferably 0.8 to 1.2 equivalents to the functional group such as an epoxy group or a (meth)acryloyl group. The equivalent of the photocuring agent relative to the curable resin is expressed as an equivalent ratio of the photocuring agent relative to the functional group.

[0203] The photoradical generator is not particularly limited as long as it can directly or indirectly generate radicals by light irradiation.

[0204] Examples of the photoradical generator include imidazole compounds, diazo compounds, bisimidazole compounds, N-arylglycine compounds, organic azide compounds, titanocene compounds, aluminate compounds, organic peroxides, N-alkoxypyridines, Salt compounds, and thioxanthone compounds. Examples of azide compounds include p-azidobenzaldehyde, p-azidoacetophenone, p-azidobenzoic acid, p-azidobenzylideneacetophenone, 4,4'-diazidechalcone, 4,4'-diazidediphenylsulfide, and 2,6-bis(4'-azidobenzylidene)-4-methylcyclohexanone. Examples of diazo compounds include 1-diazo-2,5-diethoxy-4-p-tolylmercaptobenzene fluoroborate, 1-diazo-4-N,N-dimethylaminobenzene chloride, and 1-diazo-4-N,N-diethylaminobenzene fluoroborate.

[0205] Examples of the bisimidazole compound include 2,2'-bis(o-chlorophenyl)-4,5,4',5'-tetrakis(3,4,5-trimethoxyphenyl)1,2'-bisimidazole and 2,2'-bis(o-chlorophenyl)-4,5,4',5'-tetraphenyl-1,2'-bisimidazole. Examples of the titanocene compound include dicyclopentadiene-titanium-diacid chloride, dicyclopentadiene-titanium-bisphenyl, dicyclopentadiene-titanium-bis(2,3,4,5,6-pentafluorophenyl), dicyclopentadiene-titanium-bis(2,3,5,6-tetrafluorophenyl), dicyclopentadiene-titanium-bis(2,4,6-trifluorophenyl), dicyclopentadiene-titanium-bis(2,6-difluorophenyl), dicyclopentadiene-titanium-bis(2,4-difluorophenyl), bis(methylcyclopentadiene)-titanium-bis(2,3,4,5,6-pentafluorophenyl), bis(methylcyclopentadiene)-titanium-bis(2,3,5,6-tetrafluorophenyl), bis(methylcyclopentadiene)-titanium-bis(2,6-difluorophenyl), and dicyclopentadiene-titanium-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl).

[0206] Examples of the photoradical generator include 1,3-di(tert-butyldioxycarbonyl)benzophenone, 3,3',4,4'-tetra(tert-butyldioxycarbonyl)benzophenone, 3-phenyl-5-isoxazolone, 2-mercaptobenzimidazole, 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone.

[0207] As these photoradical polymerization agents, they can be obtained, for example, under the trade name Irgacure TPO manufactured by BASF (the component is 2,4,6-trimethylbenzoyldiphenylphosphine oxide) (c1-1-1), under the trade name Omnirad819 manufactured by IGM RESINS (the component is bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide) (c1-1-2), and under the trade name Irgacure 184 manufactured by IGM RESINS (the component is 1-hydroxycyclohexyl phenyl ketone) (c1-1-3).

[0208]

Chemistry 5

[0209]

[0210] The photoacid generator is not particularly limited as long as it can directly or indirectly generate an acid by light irradiation.

[0211] Specific examples of the photoacid generator include triazine compounds, acetophenone derivative compounds, disulfone compounds, diazomethane compounds, sulfonic acid derivative compounds, iodine compounds, Salt, sulfonium salt, Salt, selenium salt, etc. Salts, metallocene complexes, iron aromatic complexes, etc.

[0212] As the above-mentioned photoacid generator used Salt, iodine Salts such as diphenyl iodide Hydrochloride, diphenyl iodide Trifluoromethanesulfonate, diphenyl iodide Methanesulfonate, diphenyl iodide Tosylate, diphenyl iodide Hydrobromide, diphenyl iodide Tetrafluoroborate, diphenyl iodide Hexafluoroantimonate, diphenyl iodide Hexafluoroarsenate, bis(p-tert-butylphenyl) iodide Hexafluorophosphate, bis(p-tert-butylphenyl)iodide Methanesulfonate, bis(p-tert-butylphenyl)iodide Tosylate, bis(p-tert-butylphenyl)iodide Trifluoromethanesulfonate, bis(p-tert-butylphenyl)iodide Tetrafluoroborate, bis(p-tert-butylphenyl)iodide Hydrochloride, Bis(p-chlorophenyl)iodide Hydrochloride, Bis(p-chlorophenyl)iodide Tetrafluoroborate, and further examples thereof include bis(4-tert-butylphenyl)iodide Bis(alkylphenyl)iodide hexafluorophosphate, etc. Salts, alkoxycarbonylalkoxy-trialkylaryl iodides Salts (e.g., 4-[(1-ethoxycarbonyl-ethoxy)phenyl]-(2,4,6-trimethylphenyl)-iodine Hexafluorophosphate, etc.), bis(alkoxyaryl)iodide Salts (e.g., (4-methoxyphenyl)phenyl iodide Bis(alkoxyphenyl)iodide hexafluoroantimonate Salt).

[0213] Examples of the sulfonium salt include triphenylsulfonium chloride, triphenylsulfonium bromide, tri(p-methoxyphenyl)sulfonium tetrafluoroborate, tri(p-methoxyphenyl)sulfonium hexafluorophosphonate, tri(p-ethoxyphenyl)sulfonium tetrafluoroborate, triphenylsulfonium trifluoromethanesulfonate, triphenylsulfonium hexafluoroantimonate, and triphenylsulfonium hexafluorophosphate; and sulfonium salts such as (4-phenylthiophenyl)diphenylsulfonium hexafluoroantimonate, (4-phenylthiophenyl)diphenylsulfonium hexafluorophosphate, bis[4-(diphenylsulfonyl)phenyl]sulfide-bis-hexafluoroantimonate, bis[4-(diphenylsulfonyl)phenyl]sulfide-bis-hexafluorophosphate, and (4-methoxyphenyl)diphenylsulfonium hexafluoroantimonate.

[0214] As Salts such as triphenyl chloride , triphenyl bromide , tris(p-methoxyphenyl) Tetrafluoroborate, tris(p-methoxyphenyl) Hexafluorophosphonate, tris(p-ethoxyphenyl) Tetrafluoroborate, 4-chlorobenzene diazonium hexafluorophosphate, benzyl triphenyl Hexafluoroantimonate, etc. Salt.

[0215] Examples include selenium salts such as triphenylselenium hexafluorophosphate and metallocene complexes such as (η5 or η6-isopropylbenzene)(η5-cyclopentadienyl)iron(II) hexafluorophosphate.

[0216] In addition, the following compounds can also be used as the photoacid generator.

[0217]

Chemistry 6

[0218]

[0219]

Chemistry 7

[0220]

[0221]

Chemistry 8

[0222]

[0223]

Chemistry 9

[0224]

[0225]

Chemistry 10

[0226]

[0227]

Chemistry 11

[0228]

[0229]

Chemistry 12

[0230]

[0231]

Chemistry 3

[0232]

[0233]

Chemistry 14

[0234]

[0235] As the photoacid generator, sulfonium salt compounds, iodine Salt compounds. As their anion species, CF3SO3 can be cited. - 、C4F9SO3 - 、C8F 17 SO3 - , camphorsulfonic acid anion, p-toluenesulfonic acid anion, BF4 - PF6 - 、AsF6 - and SbF6 - Etc. Anionic species such as phosphorus hexafluoride and antimony hexafluoride which exhibit strong acidity are particularly preferred.

[0236] As required, the film-forming composition of the present invention may include conventional additives. Such additives include pigments, colorants, thickeners, sensitizers, defoamers, coating improvers, lubricants, stabilizers (antioxidants, heat stabilizers, light stabilizers, etc.), plasticizers, dissolution promoters, fillers, antistatic agents, etc. These additives can be used alone or in combination of two or more.

[0237] Examples of a method for applying the film-forming composition of the present invention include flow coating, spin coating, spray coating, screen printing, casting, bar coating, curtain coating, roll coating, gravure coating, dipping, and slit coating.

[0238] In the present invention, the photo-coating composition (film-forming composition) can be cured by applying the composition onto a substrate and irradiating the composition with light. In addition, heating may be performed before or after the irradiation with light.

[0239] The thickness of the coating film can be selected from the range of about 0.01μm to 10mm depending on the use of the cured product. For example, when used in a photoresist, it can be set to about 0.05-10μm (especially 0.1-5μm), when used in a printed circuit board, it can be set to about 5μm to 5mm (especially 100μm to 1mm), and when used in an optical film, it can be set to about 0.1-100μm (especially 0.3-50μm).

[0240] When a transparent film is obtained, the visible light transmittance of the film can be 80% or more, or 90% or more, and can typically be 90 to 96%.

[0241] When a photoacid generator is used, the light used for irradiation or exposure may be, for example, gamma rays, X-rays, ultraviolet rays, visible rays, etc., usually visible light or ultraviolet rays, and ultraviolet rays are particularly used in most cases. The wavelength of the light is, for example, 150 to 800 nm, preferably 150 to 600 nm, and more preferably about 150 to 400 nm. The amount of irradiation light varies depending on the thickness of the coating film, for example, 2 to 20,000 mJ / cm 2 , preferably 5 to 5000 mJ / cm 2 As a light source, it can be selected according to the type of exposure light. For example, in the case of ultraviolet light, a low-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a deuterium lamp, a halogen lamp, a laser (helium-cadmium laser, excimer laser, etc.) can be used. By such light irradiation, the curing reaction of the aforementioned composition can be carried out.

[0242] When a thermal acid generator is used, or when a photoacid generator is used and the coating film is heated as needed after light irradiation, for example, at 60 to 350° C., preferably at about 100 to 300° C. The heating time can be selected from a range of 3 seconds or more (for example, 3 seconds to about 5 hours), for example, 5 seconds to 2 hours, preferably about 20 seconds to 30 minutes, and usually about 1 minute to 3 hours (for example, 5 minutes to 2.5 hours).

[0243] Furthermore, when forming a pattern or image (for example, when manufacturing a printed circuit board, etc.), the coating film formed on the substrate can be subjected to pattern exposure, and the pattern exposure can be performed by laser scanning or by irradiating light through a photomask. The non-irradiated area (unexposed part) generated by such pattern exposure is developed (or dissolved) with a developer to form a pattern or image.

[0244] As the developer, an aqueous alkali solution or an organic solvent can be used.

[0245] Examples of the aqueous alkali solution include aqueous solutions of alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, potassium carbonate, and sodium carbonate; aqueous solutions of quaternary ammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and choline; and aqueous solutions of amines such as ethanolamine, propylamine, and ethylenediamine.

[0246] Generally, the alkaline developer is an aqueous solution of 10% by mass or less, preferably 0.1 to 3.0% by mass. Furthermore, alcohols or surfactants may be added to the developer, preferably 0.05 to 10 parts by mass, respectively, relative to 100 parts by mass of the developer.

[0247] Among them, a 0.1 to 2.38 mass % aqueous solution of tetramethylammonium hydroxide can be used.

[0248] In addition, as the organic solvent of the developer, a general organic solvent can be used, for example, acetone, acetonitrile, toluene, dimethylformamide, methanol, ethanol, isopropanol, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol propyl ether, propylene glycol butyl ether, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, propylene glycol butyl ether acetate, ethyl lactate, cyclohexanone, etc., and these can be used as a mixture of one or more. In particular, propylene glycol methyl ether, propylene glycol methyl ether acetate, ethyl lactate, etc. are preferably used.

[0249] In the present invention, a close adhesion promoter may be added for the purpose of improving the close adhesion to the substrate after development. Examples of these close adhesion promoters include chlorosilanes such as trimethylchlorosilane, dimethylvinylchlorosilane, methyldiphenylchlorosilane, and chloromethyldimethylchlorosilane, alkoxysilanes such as trimethylmethoxysilane, dimethyldiethoxysilane, methyldimethoxysilane, dimethylvinylethoxysilane, diphenyldimethoxysilane, and phenyltriethoxysilane, hexamethyldisilazane, N,N'-bis(trimethylsilyl)urea, dimethyltrimethylsilylamine, and trimethylsilylimidazole, and silazanes such as vinyltrichlorosilane, 3- Silanes such as 3-chloropropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-(N-piperidyl)propyltrimethoxysilane, benzotriazole, benzimidazole, indazole, imidazole, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, 2-mercaptobenzoxazole, ureaazole, thiouracil, mercaptoimidazole, mercaptopyrimidine, or urea such as 1,1-dimethylurea and 1,3-dimethylurea, or thiourea compounds. One or a combination of two or more of the above-mentioned adhesion promoters can be used. The addition amount of these adhesion promoters is usually 18% by mass or less, preferably 0.0008 to 9% by mass, or preferably 0.04 to 9% by mass, calculated on the solid content.

[0250] The present invention may also contain a sensitizer. Examples of usable sensitizers include anthracene, phenothiazine, perylene, thioxanthone, benzophenone thioxanthone, and the like. Further, examples of sensitizing pigments include thiopyran (thiopyrylium) salt pigments, merocyanidin pigments, quinoline pigments, styrylquinoline pigments, ketocoumarin pigments, thiocyanin pigments, xanthene pigments, oxonol pigments, cyanine pigments, rhodamine pigments, pyran Salt-based pigments, etc. Anthracene-based sensitizers are particularly preferred. By using them together with a cationic curing catalyst (radiation-sensitive cationic polymerization initiator), the sensitivity can be dramatically improved, and they also have a free radical polymerization initiation function. When the cationic curing system of the present invention and the free radical curing system are used, the catalyst species can be simplified. As specific anthracene compounds, dibutoxyanthracene, dipropoxyanthraquinone, etc. are effective. The amount of the sensitizer added is 0.01 to 20% by mass based on the solid content, preferably 0.01 to 10% by mass.

[0251] The composition of the present invention can be photocured or thermally cured using a photoradical generator, a thermal radical generator, a photoacid generator, or a thermal acid generator. When a photoacid generator or a thermal acid generator is used, for example, since a commonly used epoxy curing agent (such as an amine or anhydride) is not used, or even if these curing agents are used, their content is extremely small, the storage stability of the present composition can be improved.

[0252] It was found that the above composition is suitable for photocationic polymerization. It has a faster curing speed than the liquid epoxy compound (e.g., alicyclic epoxy compound having an epoxy cyclohexyl ring) of the previous product. Due to the fast curing speed, the amount of acid generator added can be reduced, or a weak acid acid generator can be used. The reduction of acid generator is important in metal corrosion protection because acid active species remain after UV irradiation. Due to the fast curing speed, it can be cured in a thick film. Curing by UV irradiation can be applied to materials (machine materials) with poor heat resistance.

[0253] The thermosetting material and photocuring material formed using the film-forming composition of the present invention have the characteristics of rapid curing, transparency, and small shrinkage upon curing, and can be used for coating or bonding electronic parts, optical parts (anti-reflective films), and precision mechanism parts.

[0254] The above-mentioned component (varnish) can be suitably used as a hard coating agent or a composition for nanoimprint.

[0255] In addition, as other uses, it can be used for bonding parts such as mobile phone or camera lenses, light emitting diodes (LEDs), semiconductor lasers (LDs), liquid crystal panels, biochips, camera lenses or prisms, magnetic parts of hard disks of computers, etc., reading parts of CD and DVD players (the part that reads light information reflected from the disc), speaker cones and coils, motor magnets, circuit boards, electronic parts, and parts inside the engine of automobiles, etc.

[0256] As a hard coating material for protecting the surface of vehicle bodies, lamps or electrical products, building materials, plastics, etc., it can be applied to, for example, vehicle bodies of automobiles and motorcycles, lenses or mirrors of headlights, plastic lenses of glasses, mobile phones, game consoles, optical films, ID cards, etc.

[0257] Examples of ink materials for printing on metals such as aluminum, plastics, and the like include inks suitable for printing on cards such as credit cards and membership cards, switches and keyboards of electronic products or OA equipment, and inks for inkjet printers for CDs and DVDs.

[0258] Examples of applications include: technology for curing resins in combination with three-dimensional CAD to produce complex three-dimensional objects, application to optical shaping for model making of industrial products, application to coating, bonding, optical waveguides, thick film resists, etc. of optical fibers.

[0259] In addition, the film-forming composition of the present invention can be suitably used as an insulating resin for electronic materials such as antireflection films, semiconductor sealing materials, adhesives for electronic materials, printed circuit board materials, interlayer insulating film materials, and sealing materials for power modules, or an insulating resin used in high-voltage equipment such as generator coils, transformer coils, and gas-insulated switchgear.

[0260] [Example]

[0261] [Total metal oxide concentration]

[0262] The sol was weighed in a crucible, heated at 110° C. for 30 minutes to remove the solvent, and then pre-dried. The crucible was calcined at 600° C. for 30 minutes. The crucible was weighed, and the total metal oxide concentration was calculated from the weight of the residue.

[0263] [X-ray diffraction measurement]

[0264] The sol was dried on a hot plate at 110° C. and pulverized using a mortar and pestle for 15 minutes to obtain a dry powder. The dry powder was measured using an XRD device (Rigaku Corporation, trade name MiniFlex600) to obtain an X-ray diffraction pattern.

[0265] [Viscosity]

[0266] The viscosity was determined by a BM type viscometer (25° C.).

[0267] [Average particle size measured by dynamic light scattering (dynamic light scattering particle size, DLS average secondary particle size)]

[0268] The sol was diluted with a dispersion solvent and measured using a dynamic light scattering device (manufactured by Malvern Instruments Ltd, trade name

[0269] Zetasizer) using the parameters of the solvent for measurement.

[0270] [Average primary particle size measured by transmission electron microscopy]

[0271] The sol was dropped onto a copper mesh and dried, and observed using a transmission electron microscope (manufactured by JEOL Ltd., trade name JEM-1020) at an accelerating voltage of 100 kV. 100 particles were measured and the average value was determined as the average primary particle size.

[0272] [ 31 P-NMR test]

[0273] On the colloidal particles in sol 31 P-NMR is measured by the following method. (Preparation of Phosphoric Acid-treated Colloidal Particle Dry Powder)

[0274] The surface of the colloidal particles was treated with phosphoric acid by adding 85% phosphoric acid aqueous solution in an amount of 3.0% by mass relative to the solid content of the colloidal particles to 10.0 g of the sol and stirring for 0.5 hours. Next, the obtained sol was thoroughly washed by ultrafiltration to remove phosphoric acid that was not bonded to the particles. The washed sol was dried on a hot plate at 60° C. for 3 hours and the dried powder was crushed in an agate mortar for 10 minutes to prepare a dry powder of the phosphoric acid-treated colloidal particles.

[0275] (By solid state NMR 31 P-NMR analysis)

[0276] The dried powder was encapsulated in a sample tube (2.5 mm in diameter) used for solid NMR measurement and measured by DD / MAS method. 31 P solid-state NMR measurement: A nuclear magnetic resonance apparatus (trade name: AVANCE3 (manufactured by Bruker, 500 MHz)) was used as the apparatus, and the measurement was performed under the following conditions.

[0277] Probe diameter: 4.0mm

[0278] Rotation speed: 30000Hz

[0279] Relaxation waiting time: 10s

[0280] Cumulative times: 8000 times

[0281] Based on the obtained spectrum, peaks derived from metal species bonded to phosphoric acid were separated, and the presence or absence of a main peak derived from Ti atoms as a core component of the colloidal particles (Ti-OP) was examined.

[0282] Ti-OP: δ = 3 to 5 ppm

[0283] The result in which the peak of Ti-OP was confirmed for the particle was marked as "○", and the result in which the peak was not confirmed was marked as "×".

[0284] [Residual color rate of pigment by UV irradiation at 490nm]

[0285] In an aqueous dispersion or methanol dispersion of inorganic oxide microparticles equivalent to 0.05 g in terms of solid content weight, a solvent is appropriately added in such a manner that water / methanol = 1 / 1 (weight ratio) and the solid content concentration is 0.5 wt%. Next, the obtained dispersion and a glycerol solution of sunset yellow dye with a solid content concentration of 0.02 wt% are mixed in such a manner that the weight ratio (dispersion weight / glycerol solution weight) becomes 1 / 3 to prepare a sample, and the sample is placed in a quartz cell with a depth of 1 mm, a width of 1 cm, and a height of 5 cm. Next, an ultraviolet lamp (SLUV-6 manufactured by ASONE) in the wavelength region of I rays (wavelength 365 nm) is selected, and the surface of the aforementioned quartz cell with a width of 1 cm and a height of 5 cm is irradiated at an intensity of 0.4 mW / cm at 25°C. 2 The sample was irradiated with ultraviolet light (365 nm wavelength) for 30 minutes. The absorbance (A0) of the sample before irradiation with ultraviolet light at a wavelength of 490 nm and the absorbance (A1) after irradiation with ultraviolet light were measured using an ultraviolet-visible near-infrared spectrophotometer (manufactured by Shimadzu Corporation, trade name UV-3600), and the residual color rate of the dye was calculated according to the following formula.

[0286] Residual color rate (%) = A1 / A0×100

[0287] [Particle refractive index]

[0288] The refractive index of the colloidal particles in the sol is measured according to the following steps i) to iii).

[0289] i) Preparation of a coating liquid containing a sol dispersed in an organic solvent containing colloidal particles

[0290] 20.00 g of 3-glycidyloxypropyltrimethoxysilane (Momentive, trade name SILQUEST A-187T) was weighed into a plastic container, and 18.57 g of methanol and 4.57 g of 0.01 N hydrochloric acid aqueous solution were added thereto, and stirred at room temperature for 5 hours. 6.00 g of a methanol solution of 2,4-pentanedionate aluminum (Al(acac)3) (10% by mass Al(acac)3) prepared in advance was added as a curing agent and stirred for 10 minutes to prepare a partial hydrolyzate of 3-glycidyloxypropyltrimethoxysilane (concentration: 43% by mass).

[0291] The prepared partial hydrolyzate of 3-glycidyloxypropyltrimethoxysilane, the colloidal particle dispersion sol, water, methanol, and 0.25 g of a methanol solution (10% by mass of L-7604) of a leveling agent (DOWSIL trade name, L-7604) were weighed to a total of 25.00 g, put into a brown bottle, and stirred at room temperature for 30 minutes to prepare a colloidal particle organic solvent dispersion sol-containing coating liquid (solid content concentration of 10.0% by mass, colloidal particle content of 50 phr, 100 phr, 150 phr).

[0292] ii) Modulation of particle-coated membranes

[0293] About 0.5 mL of the colloid particle organic solvent dispersion sol obtained in i) was dropped onto a UV-O3 treated Si substrate, and the coating was performed using a spin coater (Mikasa (Strain), trade name Opticoat MS-B100) in such a way that the film thickness after coating became 1.0 μm. Thereafter, the film was baked on a hot plate at 80° C. for 5 minutes and heat treated in an oven at 120° C. for 1 hour to prepare a particle-coated film (particle-coated amount: 50 phr, 100 phr, 150 phr).

[0294] iii) Refractive index measurement of particle-blended films and calculation of refractive index of particles

[0295] The refractive index of the particle-blended film (particle blending amount: 50 phr, 100 phr, 150 phr) obtained in ii) was measured using an ellipsometer (manufactured by JA Woollam JAPAN Co., Ltd., multi-incident angle spectroscopic ellipsometer, trade name VASE). The refractive index of a film prepared in the same manner using only a partial hydrolyzate of 3-glycidyloxypropyltrimethoxysilane without particles was also measured. The refractive index of the particles was obtained by plotting the refractive index of the measured blended film relative to the blending amount of the particles and extrapolating the result so that the blending amount of the particles was 100% by mass.

[0296] [Dispersion stability]

[0297] After the dispersion was stored at 50°C for 1 week, samples with a particle size less than 1.2 times the particle size before the storage test were marked as "○", indicating no change; samples with a particle size change of more than 1.2 times the particle size before the storage test were marked as "×".

[0298] The cured film was formed on a urethane plastic lens substrate or a glass substrate according to the method described later, for example (Evaluation of Cured Film in Example 9 - A1) or (Evaluation of Cured Film in Example 13 - A5), and evaluated at 25°C and 50% humidity.

[0299] (1) Film refractive index

[0300] The reflectivity of the cured film formed on the glass substrate was measured using a reflectivity measuring instrument (manufactured by Olympus Corporation, trade name USPM-RU). Based on the measured reflectivity, the refractive index of the cured film was calculated using optical simulation.

[0301] (2) Transparency

[0302] The cured film formed on the urethane plastic lens substrate or the glass substrate was visually inspected for haze under a fluorescent light in a dark room. The criteria for judgment are as follows.

[0303] ○: Almost no fogging occurs.

[0304] ×: Fogging was generated and whitening was clearly observed.

[0305] (3) Optical rotation resistance

[0306] An ultraviolet fluorescent lamp accelerated weathering tester (manufactured by Q-Lab, trade name QUV) with a packaged UV-A lamp was used at 0.89 W / m 2 The cured film formed on the urethane plastic lens or glass substrate was irradiated with ultraviolet light for 24 hours under the condition of 100 nm (340 nm). The judgment criteria are as follows.

[0307] ○: No cracks or film peeling were confirmed.

[0308] ×: Cracks or film peeling were confirmed.

[0309] (4) Scratch resistance

[0310] The surface of the cured film formed on the urethane plastic lens substrate or the glass substrate was rubbed with steel wool #0000, and the presence or absence of scratches on the cured film was visually inspected in a bright room under a fluorescent lamp. In addition, the scratch resistance test conditions were set to 1 time / 10 seconds and a load of 1 kg. The judgment criteria are as follows.

[0311] ○: No scratches were visually confirmed.

[0312] ×: Scratches are visually confirmed.

[0313] (5) Nanoimprinting

[0314] The colloidal particles organic solvent dispersion sol is applied to a quartz substrate with a coating liquid by spin coating, and heated at 100 ° C for 1 minute using a hot plate to make a desolvated film. Using a nanoimprinter (Mingchang Machinery (Strain), trade name NM-0801HB), the obtained film is pressed with 1000N on a quartz mold ((Strain) KYODOINTERNATIONAL, trade name DTM-2-1) treated with a demolding process, irradiated with ultraviolet rays and transferred the concave-convex pattern while curing it. The obtained cured film is peeled off from the mold, and the formation pattern is observed using SEM (Japan Electronics (Strain), trade name JSM-6010LV). The judgment criteria are as follows.

[0315] ○: The pattern was transferred and the imprintability was good.

[0316] ×: The pattern was not transferred and the imprintability was poor.

[0317] (Reference Example 1): Preparation of Titanium Oxide-Tin Dioxide Composite Oxide Colloidal Particles (A1) as Cores (Core Body)

[0318] 319.5 g of 25% by mass tetramethylammonium hydroxide aqueous solution was dissolved in 947.1 g of pure water, and then 7.4 g of metastannic acid (6.3 g in terms of SnO2), 236.6 g of titanium tetraisopropoxide (66.6 g in terms of TiO2), and 82.0 g of oxalic acid dihydrate (58.5 g in terms of oxalic acid) were added under stirring. The mixed solution was maintained at 80°C for 2 hours, and then the pressure was reduced to 580 Torr and maintained for another 2 hours to prepare a mixed solution. The mixed solution was placed in a glass-lined autoclave container, hydrothermally treated at 140°C for 5 hours, cooled to room temperature and then taken out. The obtained sol was a water-dispersed sol of titanium oxide-tin dioxide composite oxide colloidal particles (A1), and the total metal oxide concentration (TiO2 and SnO2) was 5.0% by mass, and the average primary particle size observed by transmission electron microscopy was 10 nm. The sol was dried at 110° C., and the obtained powder was subjected to X-ray diffraction analysis, which confirmed that the powder was rutile crystal.

[0319] (Reference Example 2): Preparation of Titanium Oxide-Tin Dioxide Composite Oxide Colloidal Particles (A2) as Cores

[0320] 319.5 g of 25% tetramethylammonium hydroxide aqueous solution was dissolved in 947.1 g of pure water, and then 14.8 g of metastannic acid (12.5 g in terms of SnO2), 236.6 g of titanium tetraisopropoxide (66.6 g in terms of TiO2), and 82.0 g of oxalic acid dihydrate (58.5 g in terms of oxalic acid) were added under stirring. The mixed solution was maintained at 80°C for 2 hours, and then the pressure was reduced to 580 Torr and maintained for another 2 hours to prepare a mixed solution. The mixed solution was placed in a glass-lined autoclave container, hydrothermally treated at 140°C for 5 hours, and taken out after cooling to room temperature. The obtained sol is a water-dispersed sol of titanium oxide-tin dioxide composite oxide colloidal particles (A2), and the total metal oxide concentration (TiO2 and SnO2) is 5.0% by mass, and the average primary particle size observed by transmission electron microscopy is 10 nm. The obtained sol was dried at 110° C., and the obtained powder was subjected to X-ray diffraction analysis, which confirmed that it was a rutile crystal.

[0321] (Reference Example 3): Preparation of titanium oxide colloidal particles (A3) serving as cores (core bodies)

[0322] 319.5 g of 25% by mass tetramethylammonium hydroxide aqueous solution was dissolved in 947.1 g of pure water, and 236.6 g of titanium tetraisopropoxide (66.6 g in terms of TiO2) and 82.0 g of oxalic acid dihydrate (58.5 g in terms of oxalic acid) were added under stirring. The mixed solution was maintained at 80°C for 2 hours, and then the pressure was reduced to 580 Torr and maintained for another 2 hours to prepare a mixed solution. The mixed solution was placed in a glass-lined autoclave container, hydrothermally treated at 140°C for 5 hours, and then taken out after cooling to room temperature. The obtained sol was a water-dispersed sol of titanium oxide colloidal particles (A3), with a total metal oxide concentration (TiO2) of 5.0% by mass, and the average primary particle size observed by transmission electron microscopy was 10 nm. The obtained sol was dried at 110°C, and the obtained powder was subjected to X-ray diffraction analysis, which confirmed that it was anatase-type crystal.

[0323] (Reference Example 4): Preparation of silica-tin dioxide composite oxide colloidal particles (B1) serving as a coating

[0324] 77.2 g of JIS No. 3 sodium silicate (containing 29.8% by mass in terms of SiO2) was dissolved in 668.8 g of pure water, and then 20.9 g of sodium stannate NaSnO3·H2O (containing 55.1% by mass in terms of SnO2) was dissolved. The resulting aqueous solution was passed through a column filled with a hydrogen-type cation exchange resin (Amberlite (trade name) IR-120B). Next, 7.2 g of diisopropylamine was added to the resulting water-dispersed sol. The resulting sol was an alkaline water-dispersed sol of silica-tin dioxide composite oxide colloidal particles (B1), with a pH of 8.0, a total metal oxide concentration (SiO2, and SnO2) of 1.7% by mass, and an average primary particle size of 3 nm as observed by a transmission electron microscope.

[0325] (Reference Example 5): Preparation of antimony pentoxide colloidal particles (B2) to be coated

[0326] In a 3L container, 125g of antimony trioxide (99.5% by mass as Sb2O3), 660g of pure water and 125g of potassium hydroxide (95% by mass as KOH) were added, and 84g of 35% hydrogen peroxide was slowly added under stirring. The obtained aqueous solution of potassium antimonate was diluted to 2.2% by mass and passed through a column filled with a hydrogen-type cation exchange resin. 2.5g of diisopropylamine was added to the antimonic acid solution after ion exchange under stirring. The obtained sol was a water-dispersed sol of antimony pentoxide colloidal particles (B2), pH 10.8, Sb2O5 concentration of 1.5% by mass, and the average primary particle size observed by transmission electron microscopy was 6nm.

[0327] (Production Example 1): Preparation of titanium oxide-tin dioxide composite oxide colloidal particles (C1) modified with silicon dioxide-tin dioxide composite oxide

[0328] 1500.0 g of the water-dispersed sol of titanium oxide-tin dioxide composite oxide colloidal particles (A1) prepared in Reference Example 1 was added to 661.8 g of the water-dispersed sol of alkaline silicon dioxide-tin dioxide composite oxide colloidal particles (B1) prepared in Reference Example 4 under stirring, and the mixture was heated at 95° C. for 3 hours and then passed through a column filled with a cation exchange resin (Amberlite (trade name) IR-120B, manufactured by ORGANO Co., Ltd.).

[0329] The solid content of the sol serving as the core (core body) added to the container was 667 parts by mass relative to 100 parts by mass of the solid content of the coating sol filled in the container, and was added over 10 minutes at a rate of 66.7 parts by mass per minute.

[0330] 2.5 g of tri-n-pentylamine was added to the obtained water-dispersed sol, and the sol was concentrated by ultrafiltration to obtain a water-dispersed sol of titanium oxide-tin dioxide composite oxide colloidal particles (C1) modified with silicon dioxide-tin dioxide composite oxide. The water-dispersed sol had a pH of 5.2, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 5.0 mPa·s, and a DLS average secondary particle size of 15 nm.

[0331] (Production Example 2): Preparation of Titanium Oxide-Tin Dioxide Composite Oxide Colloidal Particles (C2) Modified with Silicon Dioxide-Tin Dioxide Composite Oxide

[0332] 1500.0 g of the water-dispersed sol of the titanium oxide-tin dioxide composite oxide colloidal particles (A1) prepared in Reference Example 1 was added to 330.9 g of the water-dispersed sol of the alkaline silicon dioxide-tin dioxide composite oxide colloidal particles (B1) prepared in Reference Example 4 under stirring, and the mixture was heated at 95° C. for 3 hours and then passed through a column filled with a cation exchange resin (Amberlite (trade name) IR-120B, manufactured by ORGANO Co., Ltd.).

[0333] The solid content of the sol serving as the core (core body) added to the container was 1340 parts by mass relative to 100 parts by mass of the solid content of the coating sol filled in the container, and was added over 20 minutes at a rate of 67 parts by mass per minute.

[0334] 2.0 g of tri-n-pentylamine was added to the obtained water-dispersed sol, and the solution was concentrated by ultrafiltration to obtain a water-dispersed sol of titanium oxide-tin dioxide composite oxide colloidal particles (C2) modified with silicon dioxide-tin dioxide composite oxide. The water-dispersed sol had a pH of 5.2, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 6.0 mPa·s, and a DLS average secondary particle size of 18 nm.

[0335] (Production Example 3): Preparation of titanium oxide-tin dioxide-zirconium oxide composite oxide colloidal particles (C3) modified with silicon dioxide-tin dioxide composite oxide

[0336] 82.7 g of zirconium oxychloride (containing 21.2% by mass in terms of ZrO2) was diluted with 501.1 g of pure water to prepare 583.8 g of an aqueous zirconium oxychloride solution (containing 3.0% by mass in terms of ZrO2), and 1750.0 g of an aqueous dispersion sol of titanium oxide-tin dioxide composite oxide colloidal particles (A2) prepared in Reference Example 2 was added under stirring. Next, the mixture was heated at 95° C. for 5 hours for hydrolysis to obtain an aqueous dispersion sol of titanium oxide-tin dioxide-zirconium oxide composite oxide colloidal particles having a thin film layer of zirconium oxide formed on the surface.

[0337] To 2330.0 g of the obtained water-dispersed sol, 1852.9 g of the water-dispersed sol of the alkaline silica-tin dioxide composite oxide colloidal particles (B1) prepared in Reference Example 4 was added under stirring, and the mixture was passed through a column filled with 500 ml of an anion exchange resin (Amberlite (trade name) IRA-410, manufactured by ORGANO Co., Ltd.). Next, the water-dispersed sol after the passage was heated at 95° C. for 5 hours, and then passed through a column filled with a cation exchange resin (Amberlite (trade name) IR-120B, manufactured by ORGANO Co., Ltd.).

[0338] The solid content of the coating sol added to the container was 30 parts by mass relative to 100 parts by mass of the solid content of the sol that became the core (core body) filled in the container, and the addition was performed over 1 minute at a rate of 30 parts by mass per minute.

[0339] 3.5 g of tri-n-pentylamine was added to the obtained water-dispersed sol, and the mixture was concentrated by ultrafiltration to obtain a water-dispersed sol of titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C3) modified with silicon dioxide-tin oxide composite oxide. The water-dispersed sol had a pH of 5.2, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 5.0 mPa·s, and a DLS average secondary particle size of 20 nm.

[0340] (Production Example 4): Preparation of Titanium Oxide-Tin Dioxide-Zirconium Oxide Composite Oxide Colloidal Particles (C4) Modified with Silicon Dioxide-Tin Dioxide Composite Oxide

[0341] 82.7 g of zirconium oxychloride (containing 21.2% by mass in terms of ZrO2) was diluted with 501.1 g of pure water to prepare 583.8 g of zirconium oxychloride aqueous solution (containing 3.0% by mass in terms of ZrO2), and 1750.0 g of the aqueous dispersion sol of the titanium oxide-tin dioxide composite oxide colloidal particles (A1) prepared in Reference Example 1 was added under stirring. Then, the mixture was heated to 95° C. for hydrolysis to obtain an aqueous dispersion sol of titanium oxide-tin dioxide-zirconium oxide composite oxide colloidal particles having a zirconium oxide thin film layer formed on the surface.

[0342] To 2330.0 g of the obtained water-dispersed sol, 2470.6 g of the water-dispersed sol of the alkaline silica-tin dioxide composite oxide colloidal particles (B1) prepared in Reference Example 4 was added under stirring, and the mixture was passed through a column filled with 500 ml of an anion exchange resin (Amberlite (trade name) IRA-410, manufactured by ORGANO Co., Ltd.). Next, the water-dispersed sol after the passage was heated at 95° C. for 5 hours, and then passed through a column filled with a cation exchange resin.

[0343] The solid content of the coating sol added to the container was 40 parts by mass relative to 100 parts by mass of the solid content of the sol that became the core (core body) filled in the container, and the addition was performed over 1 minute at a rate of 40 parts by mass per minute.

[0344] 5.6 g of tri-n-pentylamine was added to the obtained water-dispersed sol, and the mixture was concentrated by ultrafiltration to obtain a water-dispersed sol of titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C4) modified with silicon dioxide-tin oxide composite oxide. The water-dispersed sol had a pH of 5.1, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 5.0 mPa·s, and a DLS average secondary particle size of 25 nm.

[0345] (Production Example 5): Preparation of titanium oxide-tin dioxide-zirconium oxide composite oxide colloidal particles (C5) modified with silicon dioxide-tin dioxide composite oxide

[0346] 82.7 g of zirconium oxychloride (containing 21.2% by mass as ZrO2) was diluted with 501.1 g of pure water to prepare 583.8 g of zirconium oxychloride aqueous solution (containing 3.0% by mass as ZrO2), and 1750.0 g of the aqueous dispersion sol of the titanium oxide-tin dioxide composite oxide colloidal particles (A1) prepared in Reference Example 1 was added under stirring. Then, the mixture was heated to 95° C. for hydrolysis to obtain an aqueous dispersion sol of titanium oxide-tin dioxide-zirconium oxide composite oxide colloidal particles having a zirconium oxide thin film layer formed on the surface.

[0347] To 2330.0 g of the obtained water-dispersed sol, 3088.2 g of the water-dispersed sol of the alkaline silica-tin dioxide composite oxide colloidal particles (B1) prepared in Reference Example 4 was added under stirring, and the mixture was passed through a column filled with 500 ml of an anion exchange resin (Amberlite (trade name) IRA-410, manufactured by ORGANO Co., Ltd.). Next, the water-dispersed sol after the passage was heated at 95° C. for 5 hours, and then passed through a column filled with a cation exchange resin.

[0348] The solid content of the coating sol added to the container was 50 parts by mass relative to 100 parts by mass of the solid content of the sol that became the core (core body) filled in the container, and the addition was performed over 2 minutes at a rate of 25 parts by mass per minute.

[0349] 6.2 g of tri-n-pentylamine was added to the obtained water-dispersed sol, and the mixture was concentrated by ultrafiltration to obtain a water-dispersed sol of titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C4) modified with silicon dioxide-tin oxide composite oxide. The water-dispersed sol had a pH of 5.0, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 5.4 mPa·s, and a DLS average secondary particle size of 24 nm.

[0350] (Production Example 6): Preparation of titanium oxide-tin dioxide composite oxide colloidal particles (C6) modified with antimony pentoxide colloidal particles

[0351] 1500.0 g of the water-dispersed sol of the titanium oxide-tin dioxide composite oxide colloidal particles (A1) prepared in Reference Example 1 was added to 1500.0 g of the water-dispersed sol of the alkaline antimony pentoxide colloidal particles (B2) prepared in Reference Example 5 under stirring, and the mixture was heated at 95° C. for 3 hours and then passed through a column filled with a cation exchange resin.

[0352] The solid content of the sol serving as the core (core body) added to the container was 333 parts by mass relative to 100 parts by mass of the solid content of the coating sol filled in the container, and the addition was performed over 10 minutes at a rate of 33.3 parts by mass per minute.

[0353] 1.8 g of diisobutylamine was added to the obtained water-dispersed sol, and the solution was concentrated by ultrafiltration to obtain a water-dispersed sol of titanium oxide-tin dioxide composite oxide colloidal particles (C6) modified with antimony pentoxide colloidal particles. The water-dispersed sol had a pH of 5.6, a total metal oxide (TiO2, SnO2, and Sb2O5) concentration of 30.5% by mass, a viscosity of 5.5 mPa·s, and a DLS average secondary particle size of 18 nm.

[0354] (Production Example 7): Preparation of anatase-type titanium oxide colloidal particles (C7) modified with silica-tin dioxide composite oxide

[0355] 1500.0 g of the water-dispersed sol of anatase-type titanium oxide colloidal particles (A3) prepared in Reference Example 3 was added to 1764.7 g of the water-dispersed sol of alkaline silica-tin dioxide composite oxide colloidal particles (B1) prepared in Reference Example 4 under stirring, and the mixture was heated at 95° C. for 3 hours and then passed through a column filled with a cation exchange resin.

[0356] The solid content of the sol serving as the core (core body) added to the container was 250 parts by mass relative to 100 parts by mass of the solid content of the coating sol filled in the container, and the addition was performed over 10 minutes at a rate of 25.0 parts by mass per minute.

[0357] 4.5 g of diisobutylamine was added to the obtained water-dispersed sol, and the mixture was concentrated by ultrafiltration to obtain a water-dispersed sol of anatase-type titanium oxide colloidal particles (C7) modified with a silica-tin oxide composite oxide. The water-dispersed sol had a pH of 5.2, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 6.5 mPa·s, and a DLS average secondary particle size of 28 nm.

[0358] (Production Example 8): Preparation of titanium oxide-tin dioxide composite oxide colloidal particles (C8) whose core surfaces are modified with polyoxyethylene alkyl ether phosphate

[0359] 15.0 g of polyoxyethylene alkyl ether phosphate (RS-710 manufactured by Toho Chemical Industry Co., Ltd.) as a surface modifier was added to 1500.0 g of the water-dispersed sol of the titanium oxide-tin dioxide composite oxide colloidal particles (A1) prepared in Reference Example 1 under stirring to modify the particle surface.

[0360] The obtained sol was concentrated by ultrafiltration to obtain a water-dispersed sol of titanium oxide-tin dioxide composite oxide colloidal particles (C8) whose core surface was modified by polyoxyethylene alkyl ether phosphate. The water-dispersed sol had a pH of 2.8, a total metal oxide (TiO2, SnO2) concentration of 30.0% by mass, a viscosity of 6.5 mPa·s, and a DLS average secondary particle size of 26 nm.

[0361] (Production Example 9): Preparation of Titanium Oxide-Tin Dioxide Composite Oxide Colloidal Particles (C9) Modified with Silicon Dioxide-Tin Dioxide Composite Oxide

[0362] 1500.0 g of the water-dispersed sol of titanium oxide-tin dioxide composite oxide colloidal particles (A1) prepared in Reference Example 1 was added to 4411.8 g of the water-dispersed sol of alkaline silicon dioxide-tin dioxide composite oxide colloidal particles (B1) prepared in Reference Example 4 under stirring, and the mixture was heated at 95° C. for 3 hours and then passed through a column filled with a cation exchange resin (Amberlite (trade name) IR-120B, manufactured by ORGANO Co., Ltd.).

[0363] The solid content of the sol serving as the core (core body) added to the container was 100 parts by mass relative to 100 parts by mass of the solid content of the coating sol filled in the container, and the addition was performed over 10 minutes at a rate of 10 parts by mass per minute.

[0364] 3.1 g of tri-n-pentylamine was added to the obtained water-dispersed sol, and the solution was concentrated by ultrafiltration to obtain a water-dispersed sol of titanium oxide-tin dioxide composite oxide colloidal particles (C1) modified with silicon dioxide-tin dioxide composite oxide. The water-dispersed sol had a pH of 5.2, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 5.0 mPa·s, and a DLS average secondary particle size of 20 nm.

[0365] (Production Example 10): Preparation of titanium oxide-tin dioxide-zirconium oxide composite oxide colloidal particles (C10) modified with silicon dioxide-tin dioxide composite oxide

[0366] 82.7 g of zirconium oxychloride (containing 21.2% by mass as ZrO2) was diluted with 501.1 g of pure water to prepare 583.8 g of zirconium oxychloride aqueous solution (containing 3.0% by mass as ZrO2), and 1750.0 g of the aqueous dispersion sol of the titanium oxide-tin dioxide composite oxide colloidal particles (A1) prepared in Reference Example 1 was added under stirring. Then, the mixture was heated to 95° C. for hydrolysis to obtain an aqueous dispersion sol of titanium oxide-tin dioxide-zirconium oxide composite oxide colloidal particles having a zirconium oxide thin film layer formed on the surface.

[0367] To 2330.0 g of the obtained water-dispersed sol, 6176.4 g of the water-dispersed sol of the alkaline silica-tin dioxide composite oxide colloidal particles (B1) prepared in Reference Example 4 was added under stirring, and the mixture was passed through a column filled with 500 ml of an anion exchange resin (Amberlite (trade name) IRA-410, manufactured by ORGANO Co., Ltd.). Next, the water-dispersed sol after the passage was heated at 95° C. for 5 hours, and then passed through a column filled with a cation exchange resin.

[0368] The solid content of the coating sol added to the container was 100 parts by mass relative to 100 parts by mass of the solid content of the sol that would become the core (core body) filled in the container, and the addition was performed over 5 minutes at a rate of 20 parts by mass per minute.

[0369] 10.2 g of tri-n-pentylamine was added to the obtained water-dispersed sol, and the solution was concentrated by ultrafiltration to obtain a water-dispersed sol of titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C10) modified with silicon dioxide-tin oxide composite oxide. The water-dispersed sol had a pH of 5.4, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 5.8 mPa·s, and a DLS average secondary particle size of 21 nm.

[0370] (Example 1)

[0371] 100 g of the water-dispersed sol of the titanium oxide-tin dioxide composite oxide colloidal particles (C1) modified with the silicon dioxide-tin dioxide composite oxide obtained in Manufacturing Example 1 was replaced with methanol by using a rotary evaporator to obtain a methanol-dispersed sol of the titanium oxide-tin dioxide composite oxide colloidal particles (C1) modified with the silicon dioxide-tin dioxide composite oxide. Under stirring, 1.52 g of polyoxyethylene alkyl ether phosphate (manufactured by Toho Chemical Industry Co., Ltd.: trade name RS-710) as a surface modifier was added to the obtained sol 100 g, and the particles were surface-modified by reflux heating at 65°C for 5 hours. The surface-modified methanol-dispersed sol had a pH of 4.5, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 20.5% by mass, a viscosity of 2.3 mPa·s, and a DLS average secondary particle size of 16 nm. In addition, by 31 The PO-Ti measured by P-NMR was "bonded", the residual color rate was 54%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.26, the particle refractive index was 2.25, and the dispersion stability was "○".

[0372] Figure 1 The titanium oxide-tin dioxide composite oxide colloidal particles (C1) modified with silicon dioxide-tin dioxide composite oxide used in Example 1 are 31In the P-NMR spectrum, the shell layer covering the core body is partially missing, and there is a portion where the core body is exposed. When the core-shell type modified metal oxide particles are in contact with an aqueous phosphoric acid solution, a peak of (Ti-OP) bonds between the Ti atoms of the core body and the P atoms present in the phosphoric acid of the shell layer via oxygen atoms is confirmed at about δ=3 to 5 ppm, and the (Ti-OP) bond is recorded as "bonding". That is, in the core-shell type metal oxide particles, the shell layer covering the core body is partially missing, and the core body is exposed.

[0373] (Example 2)

[0374] In Example 1, the sol was prepared in the same manner as in Example 1 except that the colloidal particles were changed to (C2) obtained in Preparation Example 2. At this time, the methanol-dispersed sol had a pH of 4.2, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 30.5 mass %, a viscosity of 4.5 mPa@s, and a DLS average secondary particle size of 45 nm. 31 The PO-Ti measured by P-NMR was "bonded", the residual color rate was 22%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.18, the particle refractive index was 2.30, and the dispersion stability was "○".

[0375] (Example 3)

[0376] In Example 1, the sol was prepared in the same manner as in Example 1 except that the colloidal particles were changed to (C3) obtained in Preparation Example 3. At this time, the methanol-dispersed sol had a pH of 4.5, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5 mass %, a viscosity of 4.5 mPa@s, and a DLS average secondary particle size of 28 nm. 31 The PO-Ti measured by P-NMR was "bonded", the residual color ratio was 88%, (metal oxide other than titanium oxide) / (titanium oxide) was 0.85, the particle refractive index was 2.10, and the dispersion stability was "○".

[0377] (Example 4)

[0378] In Example 1, the sol was prepared in the same manner as in Example 1 except that the colloidal particles were changed to (C4) obtained in Preparation Example 4. At this time, the methanol-dispersed sol had a pH of 4.6, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5 mass %, a viscosity of 4.5 mPa@s, and a DLS average secondary particle size of 21 nm. 31The PO-Ti measured by P-NMR was "bonded", the residual color rate was 98%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.83, the particle refractive index was 2.10, and the dispersion stability was "○".

[0379] (Example 5)

[0380] In Example 1, the sol was prepared in the same manner as in Example 1 except that the colloidal particles were changed to (C5) obtained in Preparation Example 5. At this time, the methanol-dispersed sol had a pH of 4.4, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5 mass %, a viscosity of 4.5 mPa@s, and a DLS average secondary particle size of 29 nm. 31 The PO-Ti measured by P-NMR was "bonded", the residual color rate was 98%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.97, the particle refractive index was 2.00, and the dispersion stability was "○".

[0381] (Example 6)

[0382] In Example 1, the sol was prepared in the same manner as in Example 1 except that the colloidal particles were changed to (C6) obtained in Preparation Example 6. At this time, the methanol-dispersed sol had a pH of 4.0, a total metal oxide (TiO2, SnO2, and Sb2O5) concentration of 20.5 mass %, a viscosity of 2.5 mPa@s, and a DLS average secondary particle size of 20 nm. 31 The PO-Ti measured by P-NMR was "bonded", the residual color rate was 10%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.42, the particle refractive index was 2.25, and the dispersion stability was "○".

[0383] (Example 7)

[0384] In Example 1, the sol was prepared in the same manner as in Example 1 except that the colloidal particles were changed to (C7) obtained in Preparation Example 7. At this time, the methanol-dispersed sol had a pH of 4.2, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 20.5 mass %, a viscosity of 2.3 mPa@s, and a DLS average secondary particle size of 29 nm. 31 The PO-Ti measured by P-NMR was "bonded", the residual color rate was 40%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.40, the particle refractive index was 2.20, and the dispersion stability was "○".

[0385] (Example 8)

[0386] In Example 1, the sol was prepared in the same manner as in Example 1 except that the surface modifier was changed to 2.0 g of phenyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name KBM-103). At this time, the methanol-dispersed sol had a pH of 5.9, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 30.5 mass %, a viscosity of 2.0 mPa@s, and a DLS average secondary particle size of 16 nm. 31 The PO-Ti measured by P-NMR was "bonded", the residual color ratio was 54%, (metal oxide other than titanium oxide) / (titanium oxide) was 0.26, the particle refractive index was 2.25, and the dispersion stability was "○".

[0387] (Example 9 Cured Film Evaluation-A1)

[0388] 100 g of the methanol-dispersed sol of titanium oxide-tin oxide composite colloid particles (C1) modified with silicon dioxide-tin oxide composite oxide obtained by surface modification with polyoxyethylene alkyl ether phosphate (manufactured by Toho Chemical Industry Co., Ltd.: trade name RS-710) obtained in Example 1 was used again to prepare a PGME-dispersed sol by replacing the dispersion medium with propylene glycol monomethyl ether (hereinafter, PGME) using a rotary evaporator. At this time, the PGME-dispersed sol had a pH of 4.7, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 20.5% by mass, a viscosity of 4.5 mPa@s, and a DLS average secondary particle size of 12 nm. In addition, by 31 The PO-Ti measured by P-NMR was "bonded", the residual color rate was 54%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.26, the particle refractive index was 2.25, and the dispersion stability was "○".

[0389] Next, a cured film was produced by the following method using the sol.

[0390] In a brown bottle equipped with a magnetic stirrer, 2.0 g of a mixture of dipentaerythritol hexaacrylate and dipentaerythritol pentaacrylate (manufactured by Nippon Kayaku Co., Ltd., trade name KAYARAD DPHA) and 4.9 g of PGME as a resin binder were added, and 22.9 g of the sol of Example 9 was added while stirring. Next, 0.02 g of a photoradical polymerization initiator (manufactured by BASF Co., Ltd., trade name Irgacure OXE01) and 0.3 g of a PGME solution (KP-412 concentration: 10.0 mass%) of a methacryloyl-type surface modifier (manufactured by Shin-Etsu Chemical Co., Ltd., trade name KP-412) were added and stirred for 0.5 hours to prepare a coating liquid. A glass substrate was prepared, and the coating solution was applied thereon by spin coating at room temperature of 25°C and humidity of 50% (film thickness of 1 μm). After the solvent was evaporated at 100°C for 1 minute, a high pressure mercury lamp was used to illuminate the substrate at an accumulated light intensity of 1000 mJ / cm 2 The ultraviolet light is cured in a manner to form a cured film.

[0391] The obtained cured film had a refractive index of 1.80, a transparency of "○", and a light resistance of "○". In addition, the imprintability was evaluated as "○" using the same coating liquid.

[0392] (Example 10 Cured Film Evaluation-A2)

[0393] 1.5 g of RS-710 was further added to 100 g of the methanol-dispersed sol of titanium oxide-tin oxide composite oxide colloidal particles (C1) modified with silicon dioxide-tin oxide composite oxide obtained by surface modification with polyoxyethylene alkyl ether phosphate (manufactured by Toho Chemical Industry Co., Ltd.: trade name RS-710) obtained in Example 1, and the dispersion medium was replaced with propylene glycol monomethyl ether acetate (hereinafter, PGMEA) by using a rotary evaporator to prepare a PGMEA dispersed sol. At this time, the PGMEA dispersed sol had a pH of 4.1, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 20.5% by mass, a viscosity of 5.5 mPa·s, and a DLS average secondary particle size of 20 nm. In addition, by 31 The PO-Ti measured by P-NMR was "bonded", the residual color rate was 54%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.26, the particle refractive index was 2.20, and the dispersion stability was "○".

[0394] Next, a cured film was produced. In Cured Film Evaluation-A1 of Example 9, a cured film was produced in the same manner as in Cured Film Evaluation-A1 of Example 9 except that the sol was changed to the sol of this Example 10.

[0395] The obtained cured film had a refractive index of 1.80, a transparency of "○", and a light resistance of "○". In addition, the imprintability was evaluated as "○" using the same coating liquid.

[0396] (Example 11 Cured Film Evaluation-A3)

[0397] In the preparation of the cured film evaluation-A1 of Example 9, a cured film was prepared in the same manner as in the cured film evaluation-A1 of Example 9 except that the resin binder was changed to urethane acrylate trade name UA4200 (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.).

[0398] The obtained cured film had a refractive index of 1.80, a transparency of "○", and a light resistance of "○". In addition, the imprintability was evaluated as "○" using the same coating liquid.

[0399] (Example 12 Cured Film Evaluation-A4)

[0400] In the preparation of the cured film evaluation-A1 of Example 9, a cured film was prepared in the same manner as in the cured film evaluation-A1 of Example 9 except that the resin binder was changed to Aronox MT-3010 (manufactured by Toagosei Co., Ltd.).

[0401] The obtained cured film had a refractive index of 1.80, a transparency of "○", and a light resistance of "○". In addition, the imprintability was evaluated as "○" using the same coating liquid.

[0402] (Example 13 Cured Film Evaluation-A5)

[0403] In Example 3, the sol was prepared in the same manner as in Example 3 except that the surface modifier was changed to 2.5 g of 3-methacryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name KBM-503). At this time, the methanol-dispersed sol had a pH of 5.7, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5 mass %, a viscosity of 1.8 mPa·s, and a DLS average secondary particle size of 16 nm. 31 The PO-Ti measured by P-NMR was "bonded", the residual color rate was 88%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.85, the particle refractive index was 2.00, and the dispersion stability was "○".

[0404] Next, a cured film was produced by the following method using the sol.

[0405] In a glass container equipped with a magnetic stirrer, add 25.8 g of γ-glycidyloxypropyltrimethoxysilane, and while stirring, add 6.2 g of 0.01 equivalent hydrochloric acid dropwise. After the addition is completed, stir for 0.5 hours to obtain a partial hydrolyzate of γ-glycidyloxypropyltrimethoxysilane. Next, add 22.5 g of propylene glycol monomethyl ether, 7.0 g of methanol, 85.6 g of the methanol dispersion sol of Example 13, and 2.2 g of aluminum acetylacetonate as a curing agent to the aforementioned partial hydrolyzate of γ-glycidyloxypropyltrimethoxysilane 32.0 g, and stir for 2 hours to prepare a coating liquid for hard coating. Prepare a carbamate-based plastic lens (refractive index n D =1.67) and a glass substrate, the hard coating coating liquid was applied thereon by dip coating (film thickness 3 μm), the solvent was volatilized at 80°C for 10 minutes, and then the coating film was cured by heating at 120°C for 2 hours.

[0406] The refractive index of the obtained cured film was 1.67, and the transparency was evaluated as "○", the optical resistance was evaluated as "○", and the scratch resistance was evaluated as "○".

[0407] (Example 14 Cured Film Evaluation-A6)

[0408] In Example 3, the sol was prepared in the same manner as in Example 3 except that the surface modifier was changed to 3.7 g of an allyl isocyanate skeleton silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., trade name X-12-1290). At this time, the methanol-dispersed sol had a pH of 5.7, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5 mass %, a viscosity of 1.9 mPa·s, and a DLS average secondary particle size of 18 nm. 31 The PO-Ti measured by P-NMR was "bonded", the residual color rate was 88%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.85, the particle refractive index was 2.00, and the dispersion stability was "○".

[0409] Next, a cured film was prepared. In Cured Film Evaluation-A5 of Example 13, a cured film was prepared in the same manner as in Cured Film Evaluation-A5 of Example 13 except that the sol was changed to the sol of this Example 14.

[0410] The refractive index of the obtained cured film was 1.67, and the transparency was evaluated as "○", the optical resistance was evaluated as "○", and the scratch resistance was evaluated as "○".

[0411] (Example 15 Cured Film Evaluation-A7)

[0412] 100 g of the methanol-dispersed sol of titanium oxide-tin oxide composite oxide colloidal particles (C3) modified with silicon dioxide-tin oxide composite oxide obtained by surface modification with 3-methacryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name KBM-503) used in Example 13 was used again to prepare a MEK-dispersed sol by replacing the dispersion medium with methyl ethyl ketone (hereinafter referred to as MEK) using a rotary evaporator. The obtained MEK-dispersed sol had a pH of 6.0, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 2.1 mPa·s, and a DLS average secondary particle size of 17 nm. In addition, by 31 The PO-Ti measured by P-NMR was "bonded", the residual color rate was 88%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.85, the particle refractive index was 2.00, and the dispersion stability was "○".

[0413] Next, a cured film was produced by the following method using the sol.

[0414] In a brown bottle equipped with a magnetic stirrer, 17.6 g of a mixture of dipentaerythritol hexaacrylate and dipentaerythritol pentaacrylate (manufactured by Nippon Kayaku Co., Ltd., trade name KAYARAD DPHA), 5.2 g of methanol, and 18.3 g of PGME were added as a resin binder, and 57.2 g of the sol of Example 15 was added while stirring. Next, 0.9 g of a photoradical polymerization initiator (manufactured by BASF Co., Ltd., trade name Irgacure OXE01) and 0.9 g of a PGME solution (L-7001 concentration: 2.0 mass%) of a polyether-modified silicone oil (manufactured by Dow Corning Toray Co., Ltd., trade name L-7001) were added and stirred for 0.5 hours to prepare a coating liquid. A glass substrate was prepared, and the coating solution was applied thereon by spin coating (film thickness 3 μm). After the solvent was evaporated at 80° C. for 2 minutes, a high pressure mercury lamp was used at a cumulative light intensity of 1000 mJ / cm 2 The method is to perform ultraviolet curing to form a cured film.

[0415] The refractive index of the obtained cured film was 1.67, and the transparency was evaluated as "○", the optical resistance was evaluated as "○", and the scratch resistance was evaluated as "○".

[0416] (Example 16 Cured Film Evaluation-A8)

[0417] 100 g of the methanol-dispersed sol of titanium oxide-tin oxide composite oxide colloidal particles (C1) modified with silicon dioxide-tin oxide composite oxide obtained by surface modification with an allyl isocyanate skeleton silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., X-12-1290) used in Example 14 was used again to prepare a MEK-dispersed sol by replacing the dispersion medium with MEK using a rotary evaporator. The obtained MEK-dispersed sol had a pH of 5.9, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 1.7 mPa·s, and a DLS average secondary particle size of 15 nm. In addition, by 31 The PO-Ti measured by P-NMR was "bonded", the residual color rate was 88%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.85, the particle refractive index was 2.00, and the dispersion stability was "○".

[0418] Next, a cured film was prepared. In Cured Film Evaluation-A7 of Example 15, a cured film was prepared in the same manner as in Cured Film Evaluation-A7 of Example 15 except that the sol was changed to the sol of this Example 16.

[0419] The refractive index of the obtained cured film was 1.67, and the transparency was evaluated as "○", the optical resistance was evaluated as "○", and the scratch resistance was evaluated as "○".

[0420] (Comparative Example 1 Cured Film Evaluation-B1)

[0421] 100 g of the water-dispersed sol of titanium oxide-tin dioxide composite oxide colloidal particles (C8) whose core surface is modified by polyoxyethylene alkyl ether phosphate obtained in Preparation Example 8 was replaced with methanol by using a rotary evaporator to obtain a methanol-dispersed sol of titanium oxide-tin dioxide composite oxide colloidal particles (C8) whose core surface is modified by polyoxyethylene alkyl ether phosphate. The methanol-dispersed sol had a pH of 3.5, a total metal oxide (TiO2, and SnO2) concentration of 20.5% by mass, a viscosity of 2.3 mPa·s, and a DLS average secondary particle size of 32 nm. In addition, by 31 The PO-Ti measured by P-NMR was "bonding exists", the residual color rate was 0%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 0.10, the particle refractive index was 2.10, and the dispersion stability was "×".

[0422] Figure 2 The titanium oxide-tin dioxide composite oxide colloidal particles (A1) obtained in Preparation Example 8 used in Comparative Example 1 are 31In the P-NMR spectrum, there is no shell layer covering the core body, so that the phosphoric acid aqueous solution is in direct contact with the core body, but a peak of δ=3 to 5 ppm is confirmed for the (Ti-OP) bond between the Ti atom of the core body and the P atom present in the phosphoric acid via the oxygen atom, so the (Ti-OP) bond is "bonded". That is, the (Ti-OP) bond exists in the metal oxide particle of the core body alone.

[0423] Next, a cured film was prepared. In Cured Film Evaluation-A5 of Example 13, a cured film was prepared in the same manner as in Cured Film Evaluation-A5 of Example 13, except that the weight of the metal oxide in Comparative Example 1 was changed so that the weight of the metal oxide was the same as that in Cured Film Evaluation-A5 of Example 13.

[0424] The refractive index of the obtained cured film was 1.70, the transparency was evaluated as "○", the optical resistance was evaluated as "×" and was insufficient, and the scratch resistance was evaluated as "○".

[0425] (Comparative Example 2 Cured Film Evaluation-B2)

[0426] 100 g of the water-dispersed sol of the titanium oxide-tin dioxide composite oxide colloidal particles (C9) modified with the silicon dioxide-tin dioxide composite oxide obtained in Example 9 was used to replace the dispersion medium with methanol using a rotary evaporator. Next, the solvent was replaced with PGME to obtain a PGME dispersed sol. At this time, the PGME dispersed sol had a pH of 4.7, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 20.5% by mass, a viscosity of 4.5 mPa·s, and a DLS average secondary particle size of 21 nm. In addition, by 31 PO-Ti measured by P-NMR was "non-bonded", the residual color rate was 98%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 1.38, the particle refractive index was 1.78, and the dispersion stability was "○".

[0427] Next, a cured film was produced by the following method using the sol.

[0428] In a brown bottle equipped with a magnetic stirrer, 1.3 g of a mixture of dipentaerythritol hexaacrylate and dipentaerythritol pentaacrylate (manufactured by Nippon Kayaku Co., Ltd., trade name KAYARAD DPHA) and 3.0 g of PGME as a resin binder were added, and 25.3 g of the sol of Comparative Example 2 was added while stirring. Next, 0.01 g of a photoradical polymerization initiator (manufactured by BASF Co., Ltd., trade name Irgacure OXE01) and 0.3 g of a PGME solution (KP-412 concentration of 10.0 mass%) of a methacryloyl-type surface modifier (manufactured by Shin-Etsu Chemical Co., Ltd., trade name KP-412) were added, and stirred for 0.5 hours to prepare a coating liquid. A glass substrate was prepared, and the coating liquid (film thickness 1 μm) was applied thereon by spin coating. After the solvent was volatilized at 100°C for 1 minute, a high-pressure mercury lamp was used with an accumulated light intensity of 1000 mJ / cm 2 The method is to perform ultraviolet curing to form a cured film.

[0429] The obtained cured film had a refractive index of 1.65, a transparency of "○", and an optical resistance of "○". In addition, the imprintability was evaluated as "×" using the same coating solution.

[0430] (Comparative Example 3 Cured Film Evaluation-B3)

[0431] In the cured film evaluation-A5 of Example 13, the sol was prepared in the same manner as in the cured film evaluation-A5 of Example 13 except that the sol was changed to the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C10) modified with the silicon oxide-tin oxide composite oxide obtained in Preparation Example 10. At this time, the methanol-dispersed sol had a pH of 5.7, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5% by mass, and a viscosity of 1.6 mPa·s

[0432] , DLS average secondary particle size is 22nm. 31 PO-Ti measured by P-NMR was "non-bonded", the residual color rate was 98%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 1.85, the particle refractive index was 1.70 and insufficient, and the dispersion stability was "○".

[0433] Figure 3 The titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C10) modified with the silicon dioxide-tin oxide composite oxide obtained in Preparation Example 10 used in Comparative Example 3 are 31In the P-NMR spectrum, although the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C10) modified with silicon dioxide-tin oxide composite oxide obtained in Manufacturing Example 10 are used, there is no exposed portion of the core body because the shell layer of the composite core body is fully covered. When the core-shell type modified metal oxide particles are contacted with an aqueous phosphoric acid solution, the peak of δ=3 to 5 ppm of the (Ti-OP) bond between the Ti atom of the core body and the P atom present in the phosphoric acid via the oxygen atom cannot be confirmed, so the (Ti-OP) bond is "unbonded". That is, in the core-shell type metal oxide particles, the core body is completely covered by the shell layer, and there is no portion where a part of the shell layer covering the core body is missing and the core body is exposed.

[0434] Next, a cured film was prepared. In Cured Film Evaluation-A5 of Example 13, a cured film was prepared in the same manner as in Cured Film Evaluation-A5 of Example 13 except that the sol was changed to the sol of Comparative Example 13.

[0435] The refractive index of the obtained cured film was 1.56, and the transparency was evaluated as "○", the optical resistance was evaluated as "○", and the scratch resistance was evaluated as "○".

[0436] (Comparative Example 4 Cured Film Evaluation-B4)

[0437] In the cured film evaluation B3 of Comparative Example 3, 100 g of a methanol-dispersed sol of titanium oxide-tin oxide composite oxide colloidal particles (C10) modified with silicon dioxide-tin oxide composite oxide obtained by surface modification with 3-methacryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name KBM-503) was used, and the dispersion medium was replaced with MEK by using a rotary evaporator to prepare a MEK-dispersed sol. The obtained MEK-dispersed sol had a pH of 6.2, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 2.0 mPa·s, and a DLS average secondary particle size of 25 nm. In addition, by 31 PO-Ti measured by P-NMR was "non-bonded", the residual color rate was 98%, the mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) was 1.85, the particle refractive index was 1.70, which was insufficient, and the dispersion stability was "○".

[0438] Next, a cured film was prepared. In Cured Film Evaluation-A7 of Example 15, a cured film was prepared in the same manner as in Cured Film Evaluation-A7 of Example 15 except that the sol was changed to the sol of Comparative Example 4.

[0439] The refractive index of the obtained cured film was 1.56, and the transparency was evaluated as "○", the optical resistance was evaluated as "○", and the scratch resistance was evaluated as "○".

[0440] [Industrial Applicability]

[0441] Provided are core-shell type metal oxide particles, which are compositions used to obtain coated articles with high refractive index and high formability by nanoimprinting or the like, and which are modified metal oxide particles comprising metal oxide particles containing titanium oxide as cores and metal oxide particles other than titanium oxide as shells, with the shells covering the cores in a manner that a portion of the cores is exposed; and a method for producing the same.

Claims

1. A core-shell type metal oxide particle, comprising: a core body containing metal oxide particles with an average primary particle size of 3 to 100 nm, and a shell body containing metal oxide particles with an average primary particle size of 1 to 7 nm covering the surface of the core body, wherein: The average primary particle size has a relationship of (core metal oxide particles)>(shell metal oxide particles). When the component (a) is titanium oxide and the component (b) is a metal oxide other than titanium oxide, the core is a particle consisting of the component (a) or a particle consisting of a combination of the components (a) and (b), and the shell is a particle consisting of the component (b). The core-shell metal oxide particles satisfy the following requirements A and B: Requirement A: In a test in which the core-shell type metal oxide particles are brought into contact with a compound having a P—OH bond, NMR observation shows that PO—Ti bonds are formed in the core-shell type metal oxide particles; Requirement B: The refractive index of the core-shell type metal oxide particles is 1.85 or more.

2. The core-shell type metal oxide particle according to claim 1, wherein The component (b) is at least one metal oxide particle selected from the group consisting of zirconium oxide, silicon dioxide, aluminum oxide, tin oxide, zinc oxide, iron oxide, niobium oxide, tantalum oxide, antimony oxide, and tungsten oxide.

3. The core-shell type metal oxide particle according to claim 1 or 2, wherein The mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) is in the range of 0.05 to 1.

0.

4. The core-shell type metal oxide particle according to any one of claims 1 to 3, wherein There is an intermediate layer between the core particles and the shell particles, and the intermediate layer is a metal oxide particle composed of a combination of at least one selected from the group consisting of zirconium oxide, silicon dioxide, aluminum oxide, tin oxide, zinc oxide, iron oxide, niobium oxide, tantalum oxide, antimony oxide and tungsten oxide as component (D), The core-shell type metal oxide particles have a mass ratio of (metal oxide other than titanium oxide) / (titanium oxide) in the range of 0.05 to 1.

0.

5. The core-shell type metal oxide particle according to any one of claims 1 to 4, wherein The surface of the core-shell type metal oxide particles is coated with a compound having a P—OH bond or a Si—OH bond.

6. The core-shell type metal oxide particle according to any one of claims 1 to 5, wherein The compound having a Si-OH bond is at least one silane compound selected from the group consisting of formula (1) to formula (3) or a hydrolyzate thereof, R 1 a Si(R 2 ) 4-a formula(1) 〔R 3 b Si(R 4 ) 3-b 〕2Y c Formula (2) R 5 d Si(R 6 ) 4-d formula(3) In formula (1), R 1 are alkyl, halogenated alkyl, alkenyl, aryl, or an organic group having a polyether group, epoxy group, (meth)acryloyl group, mercapto group, amino group, urea group or cyano group, and R 1 Bonded to silicon atoms through Si-C bonds, R 2 represents an alkoxy group, an acyloxy group or a halogen group, a represents an integer of 1 to 3, In formula (2) and formula (3), R 3 and R 5 are alkyl groups having 1 to 3 carbon atoms or aryl groups having 6 to 30 carbon atoms, and R 3 and R 5 They are bonded to silicon atoms through Si-C bonds, R 4 and R 6 represents an alkoxy group, an acyloxy group or a halogen group, Y represents an alkylene group, an NH group or an oxygen atom, b is an integer of 1 to 3, c is an integer of 0 or 1, and d is an integer of 1 to 3.

7. The core-shell type metal oxide particle according to any one of claims 1 to 5, wherein The compound having a P-OH bond is at least one phosphate selected from the group consisting of formula (4) to formula (6), In formulas (4) to (6), X1, X2 and X3 respectively represent an alkylene group having 2 to 20 carbon atoms, f, h and j respectively represent an integer of 1 to 100, e, g and i respectively represent an integer of 1 to 3, and Y1, Y2 and Y3 respectively represent a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms or a (meth)acryloyl group.

8. The core-shell type metal oxide particle according to claim 7, wherein The phosphoric acid ester is a polyoxyethylene C6-20 alkyl ether phosphoric acid ester having an alkyl group having 6 to 20 carbon atoms.

9. A core-shell metal oxide sol, which is a sol obtained by dispersing the core-shell metal oxide particles according to any one of claims 1 to 8 as a dispersoid in a dispersion medium consisting of an alcohol which may have an ether bond, an ester, a ketone, an amide, a hydrocarbon, a polysiloxane, a compound containing an unsaturated bond between chain carbon atoms, an ethylene oxide compound, water, or a combination thereof, wherein: The average particle size of the core-shell metal oxide sol measured by dynamic light scattering method is 5 to 500 nm. 10 . The core-shell metal oxide sol according to claim 9 , further comprising a surfactant, which is an anionic surfactant, a cationic surfactant, a nonionic surfactant or an amphoteric surfactant. 11 . The core-shell metal oxide sol according to claim 9 , further comprising a secondary or tertiary amine having a total carbon number of 5 to 35. 12 . A varnish comprising the core-shell type metal oxide particles according to claim 1 and a thermosetting resin or a photocurable resin.

13. The varnish according to claim 12, wherein The varnish is a hard coating agent or a composition for nanoimprinting.

14. A method for producing a core-shell type metal oxide sol according to any one of claims 9 to 11, comprising the following steps (i) and (ii): (i) step: a step of preparing a sol (A) and a sol (B), wherein the sol (A) uses water as a dispersion medium and contains metal oxide particles having an average primary particle size of 3 to 60 nm as measured by a nitrogen adsorption method, and the sol (B) uses water as a dispersion medium and contains metal oxide particles having an average primary particle size of 1 to 7 nm as measured by a nitrogen adsorption method; (ii) Step: A step of mixing the above-mentioned sol (A) and the above-mentioned sol (B) in the following manner, that is, mixing them at a ratio of 22 to 1000 parts by mass of the solid content of the other sol to be added to the container per minute, relative to 100 parts by mass of the solid content of the sol filled in the container.

15. The method for producing a core-shell type metal oxide sol according to claim 14, wherein: In the above step (i) or step (ii), the following step (S-1) is added: Step (S-1): a step of adding a secondary or tertiary amine having a total carbon number of 5 to 35 to the aqueous sol.

16. The method for producing a core-shell type metal oxide sol according to claim 14 or 15, wherein: After the above step (ii), at least one step selected from the following steps (T-1), (T-2) and (T-3) is further added, Step (T-1): adding at least one silane compound selected from the group consisting of formula (1) to formula (3) or at least one phosphate ester selected from the group consisting of formula (4) to formula (6) to the core-shell type metal oxide sol obtained in step (ii); (T-2) step: a step of replacing the dispersion medium of the core-shell type metal oxide sol obtained in step (ii) with a dispersion medium composed of an alcohol, ester, ketone, amide or hydrocarbon; Step (T-3): a step of adding a surfactant to the core-shell type metal oxide sol obtained in step (ii).

17. The method for producing a core-shell type metal oxide sol according to any one of claims 14 to 16, wherein The steps are, in order, step (i), step (S-1), step (ii), step (S-1), step (T-2), step (T-1), and step (T-2).

Citation Information

Patent Citations

  • Surfaceetreated product of plastics and its preparation

    JP1977016586A

  • Coating composition

    JP1978111336A

  • Copolymer for lenses of high refractive index

    JP1980013747A

  • Transparent coated composite body

    JP1987151801A

  • Coating composition containing titanium oxide

    JP1988275682A